Toner comprising a reactive charge control agent

CN116774541BActive Publication Date: 2026-10-13XEROX CORP
View PDF 43 Cites 0 Cited by

Patent Information

Application Number
CN202310223159.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-03-17
Filing Date
2023-03-09
Publication Date
2026-10-13
Estimated Expiration
2043-03-09

AI Technical Summary

Technical Problem

由于分子配体和重金属离子的毒性,这些电荷控制剂的制造和应用可能导致环境问题和健康问题

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004117549450000101
    Figure BDA0004117549450000101
  • Figure BDA0004117549450000161
    Figure BDA0004117549450000161
  • Figure BDA0004117549450000341
    Figure BDA0004117549450000341
Patent Text Reader

Abstract

The present invention provides an emulsion aggregation toner, the emulsion aggregation toner comprising: toner particles, the toner particles including at least one resin; optionally a colorant; optionally a wax; and a reactive charge control agent, the reactive charge control agent including: at least one positively charged compound, the at least one positively charged compound including a member selected from the group consisting of an amine compound having at least 3 carbon atoms, an ammonium compound having at least 3 carbon atoms, a phosphonium compound having at least 3 carbon atoms, a boronium compound having at least 3 carbon atoms, and combinations thereof; at least one reactive anchor compound, the at least one reactive anchor compound including a member selected from the group consisting of an amino group, an epoxy group, a carboxyl group, a hydroxyl group, a silanol group, a cyanide, an anhydride, an aldehyde, a ketone, a vinyl group, and combinations thereof; and wherein the charge control agent optionally further includes a negatively charged compound, the negatively charged compound including a member selected from the group consisting of an aromatic carboxylic acid, a silanol, a phenol, a pyrones, furanones, and combinations thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related patent applications

[0002] Co-assigned U.S. Patent Application No. 17 / 697,783 (Attorney’s File No. 20210493US01, entitled “Toner Comprising Charge Control Agent”, the entire contents of which are incorporated herein by reference) filed concurrently with this application describes an emulsion-aggregated toner comprising: toner particles comprising at least one resin; optional colorant; optional wax; and a charge control agent disposed on the surface of the toner particles; the charge control agent comprising a complex formed of a metal ion donor and at least one ligand selected from the group consisting of: polyaromatic acids comprising humic acids, pyranone ligands, furanone ligands, or combinations thereof.

[0003] Co-assigned U.S. Patent Application No. 17 / 697,800 (Attorney’s File No. 20210496US01, entitled “Toner Comprising Charge Control Agent”, the entire contents of which are incorporated herein by reference) filed concurrently with this application describes an emulsion-aggregated toner comprising: toner particles comprising at least one resin; optional colorant; optional wax; and a charge control agent disposed on the surface of the toner particles; the charge control agent comprising: phenylsiloxane; and a complex formed by a metal ion donor and at least one ligand selected from the group consisting of: polyaromatic acids comprising humic acids, pyranone ligands, furanones, or combinations thereof. Background Technology

[0004] This article discloses an emulsion-aggregated toner comprising: toner particles comprising at least one resin; optional colorant; optional wax; and a reactive charge control agent disposed on the surface of the toner particles; wherein the reactive charge control agent comprises: at least one positively charged compound, wherein the at least one positively charged compound comprises a member selected from the group consisting of: amine compounds having at least 3 carbon atoms, ammonium compounds having at least 3 carbon atoms, phosphonium compounds having at least 3 carbon atoms. The compound, a boronium compound having at least 3 carbon atoms, and combinations thereof; at least one reactive anchoring compound, wherein the at least one reactive anchoring compound comprises a member selected from the group consisting of: amino, epoxy, carboxyl, hydroxyl, silanol, cyanide, acid anhydride, aldehyde, ketone, vinyl, and combinations thereof; and wherein the charge control agent optionally further comprises a negatively charged compound, wherein the negatively charged compound comprises a member selected from the group consisting of: aromatic carboxylic acids, silanols, phenol, pyranones, furanones, and combinations thereof.

[0005] A color developer is also disclosed, comprising: emulsion-aggregated toner particles and a toner carrier; wherein the emulsion-aggregated toner particles comprise: at least one resin; optional colorant; optional wax; and a reactive charge control agent disposed on the surface of the toner particles; wherein the reactive charge control agent comprises: at least one positively charged compound, wherein the at least one positively charged compound comprises a member selected from the group consisting of: amine compounds having at least 3 carbon atoms, ammonium compounds having at least 3 carbon atoms, and compounds having at least 3 carbon atoms. The charge control agent comprises phosphonium compounds, boronium compounds having at least 3 carbon atoms, and combinations thereof; at least one reactive anchoring compound comprising a member selected from the group consisting of amino, epoxy, carboxyl, hydroxyl, silanol, cyanide, acid anhydride, aldehyde, ketone, vinyl, and combinations thereof; and wherein the charge control agent optionally further comprises a negatively charged compound comprising a member selected from the group consisting of aromatic carboxylic acids, silanols, phenol, pyranones, furanones, and combinations thereof.

[0006] A method for emulsion-aggregated toner is also disclosed, comprising: obtaining a latex of at least one resin; optionally, obtaining an aqueous dispersion of an optional colorant; optionally, obtaining an aqueous dispersion of an optional wax; forming a mixture of the latex of at least one resin, the aqueous dispersion of the optional colorant, and the aqueous dispersion of the optional wax; heating the mixture to a first temperature; maintaining the first temperature to form aggregated toner particles; adding a latex of a shell resin to form a shell on the aggregated particles; optionally, adding a solution of a chelating agent; stopping further aggregation and raising the temperature to a second temperature above the first temperature to cause the aggregated particles to agglomerate; cooling, optionally washing, optionally drying, and recovering the emulsion-aggregated toner particles; introducing a reactive charge control agent into the emulsion-aggregated toner particles to form an emulsion-aggregated toner containing the reactive charge control agent. The reactive charge control agent comprises: at least one positively charged compound, wherein the at least one positively charged compound comprises a member selected from the group consisting of: amine compounds having at least 3 carbon atoms, ammonium compounds having at least 3 carbon atoms, phosphonium compounds having at least 3 carbon atoms, boronium compounds having at least 3 carbon atoms, and combinations thereof; at least one reactive anchoring compound, wherein the at least one reactive anchoring compound comprises a member selected from the group consisting of: amino, epoxy, carboxyl, hydroxyl, silanol, cyanide, acid anhydride, aldehyde, ketone, vinyl, and combinations thereof; and wherein the charge control agent optionally further comprises a negatively charged compound, wherein the negatively charged compound comprises a member selected from the group consisting of: aromatic carboxylic acids, silanols, phenol, pyranones, furanones, and combinations thereof.

[0007] While the advent of chemically produced toner particles over the years has greatly improved print quality and transfer efficiency, the chemicals involved in the formulation of these particles can interact significantly during manufacturing, potentially leading to poor customer performance. Specifically, the environmental stability of both the charging rate and average charge of particles generated by the chemicals used in emulsion aggregation (EA) and raw materials can be compromised. Under low humidity conditions, typical polyester and / or styrene acrylate particles have a very high charge and require prolonged mixing with the carrier when fresh toner is combined with aged toner in the developer to allow the charge distribution to stabilize and become uniform. Conversely, the peak average charge of these particles can be very low under high humidity conditions. This presents a challenge in ensuring good print performance in all extreme environments. In conventional particle processes (extrusion / grinding), internal charge control agents (CCAs) are incorporated into the molten mixture of resins to provide improved environmental stability in the final toner. Most commercially available charge control agents (CCAs) are small molecules, either metal complexes of molecular aromatic hydroxycarboxylic acid ligands with metal ions from calcium, zinc, aluminum, iron, chromium, boron, zirconium, titanium, etc. (for negatively charged toners), or molecular azazine compounds and quaternary ammonium salts (for positively charged toners). In the EA process, it has been shown that it is difficult to incorporate similar charge control agents into particles without negatively impacting the particle method. Furthermore, molecular CCAs can leach and degrade during the EA process. Suspension polymerization of particle formulations can easily incorporate internal CCAs into the particles by using solvents in this method. The manufacture and application of these charge control agents can lead to environmental and health problems due to the toxicity of molecular ligands and heavy metal ions. There is a strong desire to develop more sustainable CCAs to modulate the charge of toner particles. An alternative approach to combat the environmental instability in EA particles is to use titanium dioxide (TiO2) as an external additive in the toner formulation. This additive tends to reduce the average charge and increase the charging rate (incorporation) under low humidity conditions without significantly affecting high humidity charging performance, thus resulting in better environmental stability. However, because TiO2 is considered to pose a potential threat to human health, regulations concerning TiO2 have recently been implemented or are expected to be implemented, such as adjusting the amount of TiO2 that can be used in toner formulations to, for example, less than 1 wt%.

[0008] Currently available toners are suitable for their intended purpose. However, improved toners are still needed. Furthermore, there is still a need for improved toners, in the embodiments of emulsion-aggregated toners, which can be prepared with reduced amounts of TiO2, or completely without TiO2, while also providing stable charging performance in all extreme environments.

[0009] In embodiments of this disclosure, appropriate components and method aspects of each of the aforementioned U.S. patents and patent publications may be selected for this disclosure. Furthermore, throughout this application, various publications, patents, and published patent applications are referenced by identification reference. The disclosures of the publications, patents, and published patent applications referenced in this application are hereby incorporated by reference to provide a more complete description of the technical level to which this invention pertains. Summary of the Invention

[0010] This invention describes an emulsion-aggregated toner comprising: toner particles comprising at least one resin; optional colorant; optional wax; and a reactive charge control agent disposed on the surface of the toner particles; wherein the reactive charge control agent comprises: at least one positively charged compound, wherein the at least one positively charged compound comprises a member selected from the group consisting of: amine compounds having at least 3 carbon atoms, ammonium compounds having at least 3 carbon atoms, and phosphonium compounds having at least 3 carbon atoms. The compound, a boronium compound having at least 3 carbon atoms, and combinations thereof; at least one reactive anchoring compound, wherein the at least one reactive anchoring compound comprises a member selected from the group consisting of: amino, epoxy, carboxyl, hydroxyl, silanol, cyanide, acid anhydride, aldehyde, ketone, vinyl, and combinations thereof; and wherein the charge control agent optionally further comprises a negatively charged compound, wherein the negatively charged compound comprises a member selected from the group consisting of: aromatic carboxylic acids, silanols, phenol, pyranones, furanones, and combinations thereof.

[0011] A color developer is also described, comprising: emulsion-aggregated toner particles and a toner carrier; wherein the emulsion-aggregated toner particles comprise: at least one resin; optional colorant; optional wax; and a reactive charge control agent disposed on the surface of the toner particles; wherein the reactive charge control agent comprises: at least one positively charged compound, wherein the at least one positively charged compound comprises a member selected from the group consisting of: amine compounds having at least 3 carbon atoms, ammonium compounds having at least 3 carbon atoms, and so on. The charge control agent comprises phosphonium compounds, boronium compounds having at least 3 carbon atoms, and combinations thereof; at least one reactive anchoring compound comprising a member selected from the group consisting of amino, epoxy, carboxyl, hydroxyl, silanol, cyanide, acid anhydride, aldehyde, ketone, vinyl, and combinations thereof; and wherein the charge control agent optionally further comprises a negatively charged compound comprising a member selected from the group consisting of aromatic carboxylic acids, silanols, phenol, pyranones, furanones, and combinations thereof.

[0012] A method for emulsion-aggregated toner is also described, the method comprising: obtaining a latex of at least one resin; optionally, obtaining an aqueous dispersion of an optional colorant; optionally, obtaining an aqueous dispersion of an optional wax; forming a mixture of the latex of at least one resin, the aqueous dispersion of the optional colorant, and the aqueous dispersion of the optional wax; heating the mixture to a first temperature; maintaining the first temperature to form aggregated toner particles; adding a shell resin latex to form a shell on the aggregated particles; optionally, adding a solution of a chelating agent; stopping further aggregation and raising the temperature to a second temperature above the first temperature to cause the aggregated particles to agglomerate; cooling, optionally washing, optionally drying, and recovering the emulsion-aggregated toner particles; introducing a reactive charge control agent into the emulsion-aggregated toner particles to form an emulsion-aggregated toner containing the reactive charge control agent. The reactive charge control agent comprises: at least one positively charged compound, wherein the at least one positively charged compound comprises a member selected from the group consisting of: amine compounds having at least 3 carbon atoms, ammonium compounds having at least 3 carbon atoms, phosphonium compounds having at least 3 carbon atoms, boronium compounds having at least 3 carbon atoms, and combinations thereof; at least one reactive anchoring compound, wherein the at least one reactive anchoring compound comprises a member selected from the group consisting of: amino, epoxy, carboxyl, hydroxyl, silanol, cyanide, acid anhydride, aldehyde, ketone, vinyl, and combinations thereof; and wherein the charge control agent optionally further comprises a negatively charged compound, wherein the negatively charged compound comprises a member selected from the group consisting of: aromatic carboxylic acids, silanols, phenol, pyranones, furanones, and combinations thereof. Detailed Implementation

[0013] This application provides an emulsion-aggregated toner containing a charge control agent, wherein in an embodiment, the charge control agent is a reactive, metal-free charge control agent. In an embodiment, the charge control agent is introduced into emulsion-aggregated toner particles to form emulsion-aggregated toner particles containing the charge control agent.

[0014] In one embodiment, a method for incorporating a charge control agent (CCA) onto the surface of toner particles is described, wherein the CCA may be added during or after an emulsion aggregation (EA) manufacturing process. In another embodiment, the emulsion aggregation toner method includes: forming a latex, agglomerating to form aggregated particles, agglomerating the aggregated particles, cooling, optionally washing, and optionally drying to prepare emulsion aggregated toner particles. In one embodiment, the charge control agent is set onto (in another embodiment, precipitated) onto the surface of the emulsion aggregated toner particles after a cooling step. In another embodiment, the charge control agent is set onto the surface of the emulsion aggregated toner particles between a cooling step and a washing step. In yet another embodiment, the charge control agent is set onto the surface of the emulsion aggregated toner particles after a drying step. In this embodiment, the charge control agent is an internal charge control agent. As used herein, an internal charge control agent refers to a charge control agent incorporated during the wet portion of the toner method. This contrasts with external additives added to the toner after drying. The term "internal charge control agent" is intended to describe a charge control agent incorporated during the wet portion of an emulsion polymerization toner process (in embodiments, during or after polymerization, and in certain embodiments, after polymerization).

[0015] Therefore, a method for incorporating a charge control agent is provided. In an embodiment, a negatively charged phenyltriethoxysilane charge control agent is incorporated into an EA process along with a positively charged aminosiloxane, the EA process providing improved charging performance in the form of increased charging rate (incorporation rate) and improved environmental stability over a wide humidity range.

[0016] In embodiments, the method herein includes depositing charge control agent molecules onto the particle surface after a drying step or between a cooling step and a washing step in an emulsion-aggregated toner method. In a preferred embodiment, the charge control agent precipitation is performed via a further redispersion process after cooling, washing, and drying the emulsion-aggregated toner particles. In an embodiment, the charge control agent comprising phenyltriethoxysilane is deposited onto the surface of the EA particles prior to washing and drying. In an embodiment, phenyltriethoxysilane is incorporated into the EA process and provides improved charging performance in the form of improved environmental stability over a wide humidity range.

[0017] In other embodiments, an aminopropylsilsesquioxane charge control agent is incorporated into the EA process along with the positively charged aminosiloxane, or incorporated after the EA process, which in embodiments provides improved charging performance in the form of increased charging rate (doping rate) and improved environmental stability over a wide humidity range.

[0018] In embodiments, the emulsion-aggregated toner of this document comprises: toner particles comprising at least one resin; optional colorant; optional wax; and a reactive charge control agent disposed on the surface of the toner particles; wherein the reactive charge control agent comprises: at least one positively charged compound, wherein the at least one positively charged compound comprises a member selected from the group consisting of: amine compounds having at least 3 carbon atoms, ammonium compounds having at least 3 carbon atoms, phosphonium compounds having at least 3 carbon atoms, etc. Boronium compounds having at least 3 carbon atoms, and combinations thereof; at least one reactive anchoring compound, wherein the at least one reactive anchoring compound comprises a member selected from the group consisting of: amino, epoxy, carboxyl, hydroxyl, silanol, cyanide, acid anhydride, aldehyde, ketone, vinyl, and combinations thereof; and wherein the charge control agent optionally further comprises a negatively charged compound, wherein the negatively charged compound comprises a member selected from the group consisting of: aromatic carboxylic acids, silanols, phenol, pyranones, furanones, and combinations thereof.

[0019] In one embodiment, the toner particles comprise a core-shell structure; and a charge control agent is disposed on the surface of the toner particle shell.

[0020] In embodiments where a positively charged compound acts as a charge control agent by neutralizing the negative charge of toner particles aggregated in an emulsion, any suitable or desired positively charged compound may be selected. In embodiments, the positively charged compound is hydrophobic. In embodiments, the charge control agent comprises at least one positively charged compound, wherein the at least one positively charged compound comprises an amine compound having at least 3 carbon atoms, an ammonium compound having at least 3 carbon atoms, a phosphonium compound having at least 3 carbon atoms, a boronium compound having at least 3 carbon atoms, and combinations thereof. In embodiments, the at least one positively charged compound comprises a member selected from the group consisting of: aromatic amine compounds, aromatic ammonium compounds, aromatic phosphonium compounds, alkylamine compounds having at least 3 to about 50 carbon atoms, alkylammonium compounds having at least 3 to about 50 carbon atoms, alkylphosphonium compounds having at least 3 to about 50 carbon atoms, alkylboron compounds having at least 3 to about 50 carbon atoms, and combinations thereof. In some embodiments, at least one positively charged compound comprises an aromatic amine, which in other embodiments is phenylamine, naphthylamine, ammonium, phosphonium, boron, and combinations thereof. In some embodiments, the positively charged compound is selected from members of the group consisting of: ammonium nitrate, alkylammonium nitrate having 3 to about 50 carbon atoms, ammonium bromide, phosphonium nitrate, phosphonium bromide, boron nitrate, boron bromide, and combinations thereof.

[0021] The charge control agent further comprises at least one anchoring compound (or functional group). In embodiments, the charge control agent further comprises at least one reactive anchoring compound, wherein the at least one reactive anchoring compound comprises a member selected from the group consisting of: amino, epoxy, carboxyl, hydroxyl, silanol, cyanide, acid anhydride, aldehyde, ketone, vinyl, and combinations thereof.

[0022] The charge control agent optionally further comprises a negatively charged compound. In embodiments, the optional negatively charged compound comprises a member selected from the group consisting of: aromatic carboxylic acids, silanols, phenols, pyranones, furans, and combinations thereof. In some embodiments, the negatively charged compound comprises a member selected from the group consisting of: benzoic acid, tert-butylbenzoic acid, salicylic acid, tert-butylsalicylic acid, phenylsilanol, tert-butylphenylsilanol, chlorophenol, bromophenol, tert-butylphenol, sulfonephenol, humic acid, dehydroacetic acid, hydroxypyranone, thiopyranone, pyranone acid, hydroxyfuranone, thiofuranone, and combinations thereof.

[0023] In one embodiment, the charge control agent comprises a member of the group consisting of phenylsilanes, amino-silsesquioxanes, and combinations thereof. In another embodiment, the charge control agent comprises a member of the group consisting of phenyltriethoxysilanes, aminopropyl-silsesquioxanes, and combinations thereof. In one embodiment, the charge control agent comprises phenyltriethoxysilane. In another embodiment, the charge control agent comprises aminopropyl-silsesquioxane.

[0024] In another embodiment, a color developer is described comprising: emulsion-aggregated toner particles and a toner carrier; wherein the emulsion-aggregated toner particles comprise: at least one resin; optional colorant; optional wax; and a reactive charge control agent disposed on the surface of the toner particles; wherein the reactive charge control agent comprises: at least one positively charged compound, wherein the at least one positively charged compound comprises a member selected from the group consisting of: amine compounds having at least 3 carbon atoms, ammonium compounds having at least 3 carbon atoms, etc. Phosphonium compounds having at least 3 carbon atoms, boronium compounds having at least 3 carbon atoms, and combinations thereof; at least one reactive anchoring compound, wherein the at least one reactive anchoring compound comprises a member selected from the group consisting of: amino, epoxy, carboxyl, hydroxyl, silanol, cyanide, acid anhydride, aldehyde, ketone, vinyl, and combinations thereof; and wherein the charge control agent optionally further comprises a negatively charged compound, wherein the negatively charged compound comprises a member selected from the group consisting of: aromatic carboxylic acids, silanol, phenol, pyranone, furanone, and combinations thereof.

[0025] In another embodiment, a method for emulsion-aggregated toner is described, the method comprising: obtaining a latex of at least one resin; optionally, obtaining an aqueous dispersion of an optional colorant; optionally, obtaining an aqueous dispersion of an optional wax; forming a mixture of the latex of at least one resin, the aqueous dispersion of the optional colorant, and the aqueous dispersion of the optional wax; heating the mixture to a first temperature; maintaining the first temperature to form aggregated toner particles; adding a shell resin latex to form a shell on the aggregated particles; optionally, adding a solution of a chelating agent; stopping further aggregation and raising the temperature to a second temperature above the first temperature to cause the aggregated particles to agglomerate; cooling, optionally washing, optionally drying, and recovering the emulsion-aggregated toner particles; introducing a reactive charge control agent into the emulsion-aggregated toner particles to form an emulsion containing the reactive charge control agent. Liquid aggregate toner particles; wherein the reactive charge control agent comprises: at least one positively charged compound, wherein the at least one positively charged compound comprises a member selected from the group consisting of: amine compounds having at least 3 carbon atoms, ammonium compounds having at least 3 carbon atoms, phosphonium compounds having at least 3 carbon atoms, boronium compounds having at least 3 carbon atoms, and combinations thereof; at least one reactive anchoring compound, wherein the at least one reactive anchoring compound comprises a member selected from the group consisting of: amino, epoxy, carboxyl, hydroxyl, silanol, cyanide, acid anhydride, aldehyde, ketone, vinyl, and combinations thereof; and wherein the charge control agent optionally further comprises a negatively charged compound, wherein the negatively charged compound comprises a member selected from the group consisting of: aromatic carboxylic acids, silanols, phenol, pyranones, furanones, and combinations thereof.

[0026] In the implementation, the toner particles include a core-shell structure, and a reactive charge control agent is disposed on the surface of the toner particle shell during the wet portion of the emulsion aggregation toner method.

[0027] Any toner resin can be used to form the toners disclosed herein. Such resins can then be produced from any suitable monomer or one or more monomers via any suitable polymerization method. In embodiments, the resin is prepared by emulsion polymerization. In embodiments, the resin can be prepared by methods other than emulsion polymerization. In further embodiments, the resin can be prepared by polycondensation.

[0028] In some embodiments, the emulsion-aggregated toner comprises toner particles having a core-shell structure. The core and shell of the toner particles may comprise any suitable or desired resin, including those described herein. In some embodiments, the particle core comprises at least one amorphous polyester, at least one crystalline polyester, an optional colorant, and an optional wax; and the particle shell comprises at least one amorphous polyester.

[0029] In embodiments, the toner compositions of this disclosure include an amorphous resin. The amorphous resin may be linear or branched. In embodiments, the amorphous resin may include at least one low molecular weight amorphous polyester resin. Low molecular weight amorphous polyester resins available from various sources may have various melting points, for example, from about 30°C to about 120°C, from about 75°C to about 115°C in embodiments, from about 100°C to about 110°C in embodiments, or from about 104°C to about 108°C in embodiments. As used herein, the low molecular weight amorphous polyester resin has a number average molecular weight (Mn), for example, from about 1,000 to about 10,000, from about 2,000 to about 8,000, from about 3,000 to about 7,000 in embodiments, and from about 4,000 to about 6,000 in embodiments, as measured by gel permeation chromatography (GPC). If measured by GPC using polystyrene standards, the weight-average molecular weight (Mw) of the resin is 50,000 or less, for example, about 2,000 to about 50,000 in one embodiment, about 3,000 to about 40,000 in another embodiment, about 10,000 to about 30,000 in another embodiment, and about 18,000 to about 21,000 in another embodiment. The molecular weight distribution (Mw / Mn) of the low molecular weight amorphous resin is, for example, about 2 to about 6, and about 3 to about 4 in another embodiment. The low molecular weight amorphous polyester resin may have an acid value of about 8 mg KOH / g to about 20 mg KOH / g, about 9 mg KOH / g to about 16 mg KOH / g in another embodiment, and about 10 mg KOH / g to about 14 mg KOH / g in another embodiment.

[0030] Examples of usable linear amorphous polyester resins may include poly(propoxylated bisphenol A cofumarate), poly(ethoxylated bisphenol A cofumarate), poly(butoxylated bisphenol A cofumarate), poly(copropoxylated bisphenol A coethoxylated bisphenol A cofumarate), poly(1,2-propanediol fumarate), poly(propoxylated bisphenol A comaleate), poly(ethoxylated bisphenol A comaleate), poly(butoxylated bisphenol A comaleate), poly(copropoxylated bisphenol A coethoxylated bisphenol A comaleate), poly(1,2-propanediol maleate), poly(propoxylated bisphenol A coitaminate), poly(ethoxylated bisphenol A coitaminate), poly(butoxylated bisphenol A coitaminate), poly(copropoxylated bisphenol A coethoxylated bisphenol A coitaminate), poly(1,2-propanediol itaconic acid), and combinations thereof.

[0031] In embodiments, suitable amorphous resins may include alkoxylated bisphenol A fumarate / terephthalate-based polyesters and copolyester resins. In embodiments, suitable amorphous polyester resins may be copoly(propoxylated bisphenol A cofumarate)-copoly(propoxylated bisphenol A coterephthalate) resins having the following formula (I):

[0032]

[0033] Where R can be a hydrogen or methyl group, m and n represent random units of the copolymer, m can be about 2 to 10, and n can be about 2 to 10. Examples of such resins and methods of their preparation include those disclosed in U.S. Patent No. 6,063,827, the disclosure of which is incorporated herein by reference in its entirety.

[0034] Examples of linear propoxylated bisphenol A fumarate resins that can be used as latex resins can be found under the trade name SPARII. TM This information is derived from Resana S / A Industrias Quimicas, Sao Paulo, Brazil. Other suitable linear resins include those disclosed in patent numbers 4,533,614, 4,957,774, and 4,533,614, each of which is incorporated herein by reference in its entirety. These resins can be linear polyester resins, including terephthalic acid, dodecyl succinic acid, trimellitic acid, fumaric acid, and alkyloxylated bisphenol A, such as, for example, bisphenol A ethylene oxide adducts and bisphenol A propylene oxide adducts. Other propoxylated bisphenol A terephthalate resins that can be used and are commercially available include GTU-FC115, which is commercially available from Kao Corporation, Japan.

[0035] In embodiments, the low molecular weight amorphous polyester resin can be a saturated or unsaturated amorphous polyester resin. Exemplary examples of saturated and unsaturated amorphous polyester resins selected for the methods and particles of this disclosure include any of a variety of amorphous polyesters, such as polyethylene terephthalate, ... Poly(hexylene isophthalate), poly(heptanediol isophthalate), poly(octylene isophthalate), polyethylene sebate, polypropylene sebate, polybutylene sebate, polyethylene adipate, polypropylene adipate, polybutylene adipate, polypentyl adipate, polyhexylene adipate, polyheptane adipate, polyoctyl adipate, polyethylene adipate, polypropylene adipate, polybutylene adipate, polypentylene adipate, polyhexylene adipate Alcohol esters, polyheptanediol glutarate, polyoctanediol glutarate, polyethylene heptanoate, polypropylene heptanoate, polybutylene heptanoate, polypentanediol heptanoate, polyhexanediol heptanoate, poly(ethoxylated bisphenol A-fumarate), poly(ethoxylated bisphenol A-succinate), poly(ethoxylated bisphenol A-adipate), poly(ethoxylated bisphenol A-glutarate), poly(ethoxylated bisphenol A-terephthalate), poly(ethoxylated bisphenol A-m- Phthalate esters), poly(ethoxylated bisphenol A-dodecenyl succinate), poly(propoxylated bisphenol A-fumarate), poly(propoxylated bisphenol A-succinate), poly(propoxylated bisphenol A-adipate), poly(propoxylated bisphenol A-glutarate), poly(propoxylated bisphenol A-terephthalate), poly(propoxylated bisphenol A-isophthalate), poly(propoxylated bisphenol A-dodecenyl succinate), SPAR (Dixie Chemicals) (Reichhold Inc.), ARAKOTE (Ciba-Geigy Corporation), HETRON TM (Ashland Chemical) (Rohm & Haas) (Reichhold Inc.) (Rohm & Haas) (Celanese Corporation) (DuPont TM ), (Polynt Composites, Inc.), and combinations thereof. Resins can also be functionalized, such as by carboxylation, sulfonation, and especially by sodium sulfonation, if desired.

[0036] Low molecular weight linear amorphous polyester resins are typically prepared by polycondensation of an organic glycol, diacid, or diester and a polycondensation catalyst. Low molecular weight amorphous resins are generally present in toner compositions in various suitable amounts, such as about 60% to about 90% by weight of toner or solids, or about 50% to about 65% by weight in embodiments.

[0037] Examples of organic diols selected for the preparation of low molecular weight resins include: aliphatic diols having about 2 to about 36 carbon atoms, such as 1,2-ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, etc.; alkali sulfonyl-aliphatic diols, such as sodium 2-sulfo-1,2-ethylenediol, lithium 2-sulfo-1,2-ethylenediol, potassium 2-sulfo-1,2-ethylenediol, sodium 2-sulfo-1,3-propanediol, lithium 2-sulfo-1,3-propanediol, potassium 2-sulfo-1,3-propanediol, mixtures thereof, etc. Aliphatic diols are selected, for example, in an amount of about 45 mol% to about 50 mol% of the resin, and base sulfo-aliphatic diols are selected in an amount of about 1 mol% to about 10 mol% of the resin.

[0038] Examples of diacids or diesters selected for the preparation of low molecular weight amorphous polyesters include dicarboxylic acids or diesters, such as terephthalic acid, phthalic acid, isophthalic acid, fumaric acid, maleic acid, itaconic acid, succinic acid, succinic anhydride, dodecyl succinic acid, dodecyl succinic anhydride, dodecenyl succinic acid, dodecenyl succinic anhydride, glutaric acid, glutaric anhydride, adipic acid, pimelic acid, octanoic acid, azelaic acid, dodecanoic acid, dimethyl terephthalate, diethyl terephthalate, dimethyl isophthalate, diethyl isophthalate, dimethyl phthalate, phthalic anhydride, diethyl phthalate, dimethyl succinate, dimethyl fumarate, dimethyl maleate, dimethyl glutarate, dimethyl adipate, dimethyl dodecyl succinate, dimethyl dodecenyl succinate, and mixtures thereof. Organic diacids or diesters are selected, for example, in amounts of about 45 mol% to about 52 mol% of the resin.

[0039] Examples of suitable polycondensation catalysts for low molecular weight amorphous polyester resins or crystalline resins (described below) include tetraalkyl titanate, dialkyl tin oxide (such as dibutyltin oxide), tetraalkyltin (such as dibutyltin dilaurate), dialkyl tin oxide hydroxide (such as butyltin oxide hydroxide), aluminum alkoxide, alkyl zinc, dialkyl zinc, zinc oxide, stannous oxide, or mixtures thereof; and these catalysts may be used, for example, in amounts from about 0.01 mol% to about 5 mol% based on the starting diacid or diester used to generate the polyester resin.

[0040] Low molecular weight amorphous polyester resins can be branched resins. As used herein, the term "branched" or "branched" includes branched resins and / or crosslinked resins. Branching agents used to form these branched resins include, for example, polyvalent polyacids such as 1,2,4-benzenetricarboxylic acid, 1,2,4-cyclohexanetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxy-2-methyl-2-methylenecarboxypropane, tetra(methylenecarboxy)methane, and 1,2,7,8-octanetetracarboxylic acid, their anhydrides, and their compounds having a molecular weight of 1 to approximately 1 Lower alkyl esters with 6 carbon atoms; polyvalent polyols, such as sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitol, pentaerythritol, dipentaerythritol, tripentaerythritol, sucrose, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, 1,3,5-trimethylolbenzene, and mixtures thereof. The amount of the selected branching agent is, for example, from about 0.1 mol% to about 5 mol% of the resin.

[0041] The resulting unsaturated polyester is reactive (e.g., crosslinkable) in two ways: (i) along the unsaturated positions (double bonds) of the polyester chain, and (ii) functional groups, such as carboxyl and hydroxyl groups, which readily undergo acid-base reactions. In embodiments, the unsaturated polyester resin is prepared by melt polycondensation or other polymerization methods using diacids and / or anhydrides and diols.

[0042] In embodiments, the low molecular weight amorphous polyester resin or a combination of low molecular weight amorphous resins may have a glass transition temperature of about 30°C to about 80°C, or in embodiments about 35°C to about 70°C. In another embodiment, the combined amorphous resin may have a melt viscosity of about 10 Pa*S to about 1,000,000 Pa*S, or in embodiments about 50 Pa*S to about 100,000 Pa*S, at about 130°C.

[0043] The amount of low molecular weight amorphous polyester resin in the toner particles of this disclosure may be present in any core, any shell or both, in the following amounts: 25% to about 50% by weight of the toner particles (i.e., toner particles excluding external additives and water), in embodiments about 30% to about 45% by weight, and in embodiments about 35% to about 43% by weight.

[0044] In embodiments, the toner composition comprises at least one crystalline resin. As used herein, “crystalline” refers to a polyester having a three-dimensional order. As used herein, “semi-crystalline resin” refers to a resin with a crystallization percentage of, for example, from about 10% to about 90%, and in embodiments from about 12% to about 70%. Furthermore, unless otherwise stated, “crystalline polyester resin” and “crystalline resin” as used below encompass both crystalline and semi-crystalline resins.

[0045] In the implementation scheme, the crystalline polyester resin is a saturated crystalline polyester resin or an unsaturated crystalline polyester resin.

[0046] Crystalline polyester resins available from various sources may have a variety of melting points, for example, from about 30°C to about 120°C, and in embodiments from about 50°C to about 90°C. The crystalline resins may have a number average molecular weight (Mn), for example, from about 1,000 to about 50,000, in embodiments from about 2,000 to about 25,000, in embodiments from about 3,000 to about 15,000, and in embodiments from about 6,000 to about 12,000, as measured by gel permeation chromatography (GPC). The weight average molecular weight (Mw) of the resin, as measured by GPC using polystyrene standards, is 50,000 or less, for example, from about 2,000 to about 50,000, in embodiments from about 3,000 to about 40,000, in embodiments from about 10,000 to about 30,000, and in embodiments from about 21,000 to about 24,000. The molecular weight distribution (Mw / Mn) of the crystalline resin is, for example, from about 2 to about 6, and in the embodiments from about 3 to about 4. The crystalline polyester resin may have an acid value of from about 2 mg KOH / g to about 20 mg KOH / g, in the embodiments from about 5 mg KOH / g to about 15 mg KOH / g, and in the embodiments from about 8 mg KOH / g to about 13 mg KOH / g.

[0047] Exemplary examples of crystalline polyester resins may include any of a variety of crystalline polyesters, such as polyethylene adipate, polypropylene adipate, polybutylene adipate, polypentylene adipate, polyhexylene adipate, polyoctylene adipate, polyethylene succinate, polypropylene succinate, polybutylene succinate, polypentylene succinate, polyhexylene succinate, polyoctylene succinate, polyethylene sebacic acid, polypropylene sebacic acid, polybutylene sebacic acid, polypentylene sebacic acid, polyhexylene sebacic acid, polyoctylene sebacic acid, polynonylene sebacic acid, and polydecylene sebacic acid. Poly(undecanoate), poly(dodecanoate), poly(ethylene dodecanoate), poly(propylene dodecanoate), poly(butylene dodecanoate), poly(pentanediol dodecanoate), poly(hexanediol dodecanoate), poly(octanediol dodecanoate), poly(nonanediol dodecanoate), poly(decanoate decanediol), poly(undecanoate), poly(dodecanoate dodecanoate), poly(ethylene glycol fumarate), poly(propylene glycol fumarate), poly(butylene fumarate), poly(pentanediol fumarate), poly(hexanediol fumarate), poly(octanediol fumarate), poly(nonanediol fumarate), poly(decanediol fumarate) ), Copolymer (5-sulfo-m-benzoyl)-Copolymer (ethylene adipate), Copolymer (5-sulfo-m-benzoyl)-Copolymer (propylene adipate), Copolymer (5-sulfo-m-benzoyl)-Copolymer (butylene adipate), Copolymer (5-sulfo-m-benzoyl)-Copolymer (pentanediol adipate), Copolymer (5-sulfo-m-benzoyl)-Copolymer (hexanediol adipate), Copolymer (5-sulfo-m-benzoyl)-Copolymer (octyl adipate), Copolymer (5-sulfo-m-benzoyl)-Copolymer (ethylene adipate), Copolymer (5-sulfo-m-benzoyl)-Copolymer (propylene adipate), Copolymer (5-sulfo-m-benzoyl)-Copolymer (butylene adipate), Copolymer (5-sulfo-m-benzoyl) )-Copolymer (pentanediol adipate), Copolymer (5-sulfo-m-benzoyl)-Copolymer (hexanediol adipate), Copolymer (5-sulfo-m-benzoyl)-Copolymer (octyl glycol adipate), Copolymer (5-sulfo-m-benzoyl)-Copolymer (ethylene glycol succinate), Copolymer (5-sulfo-m-benzoyl)-Copolymer (propylene glycol succinate), Copolymer (5-sulfo-m-benzoyl)-Copolymer (butylene glycol succinate), Copolymer (5-sulfo-m-benzoyl)-Copolymer (pentanediol succinate), Copolymer (5-sulfo-m-benzoyl)-Copolymer (hexanediol succinate), Copolymer (5-sulfo-m-benzoyl)-Copolymer (octyl glycol succinate), Copolymer (5-sulfo-m-benzoyl)-Copolymer (ethylene glycol sebate)Copolymer (5-sulfo-m-benzoyl)-copolymer (propylene sebate), Copolymer (5-sulfo-m-benzoyl)-copolymer (butylene sebate), Copolymer (5-sulfo-m-benzoyl)-copolymer (pentanediol sebate), Copolymer (5-sulfo-m-benzoyl)-copolymer (hexanediol sebate), Copolymer (5-sulfo-m-benzoyl)-copolymer (octyl glycol ... 5-Sulfo-m-benzoyl)-copolymer (ethylene adipate), 5-Sulfo-m-benzoyl)-copolymer (propylene adipate), 5-Sulfo-m-benzoyl)-copolymer (butyl adipate), 5-Sulfo-m-benzoyl)-copolymer (pentanediol adipate), 5-Sulfo-m-benzoyl)-copolymer (hexanediol adipate), and combinations thereof.

[0048] Crystalline resins can be prepared by polycondensation, in the presence of a polycondensation catalyst, by reacting a suitable organic diol with a suitable organic diacid. Typically, an equimolar stoichiometric ratio of the organic diol and the organic diacid is used; however, in some cases, where the boiling point of the organic diol is from about 180°C to about 230°C, excess diol can be used and removed during the polycondensation process. The amount of catalyst used varies and can be selected, for example, from about 0.01 mol% to about 1 mol% of the resin. Alternatively, an organic diester can be chosen instead of the organic diacid, wherein an alcohol byproduct is generated. In another embodiment, the crystalline polyester resin is poly(dodecanoic acid-co-nonanediol).

[0049] Examples of organic diols selected for the preparation of crystalline polyester resins include: aliphatic diols having about 2 to about 36 carbon atoms, such as 1,2-ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, etc.; alkali sulfonyl aliphatic diols, such as sodium 2-sulfo-1,2-ethylenediol, lithium 2-sulfo-1,2-ethylenediol, potassium 2-sulfo-1,2-ethylenediol, sodium 2-sulfo-1,3-propanediol, lithium 2-sulfo-1,3-propanediol, potassium 2-sulfo-1,3-propanediol, mixtures thereof, etc. Aliphatic diols are selected, for example, in an amount of about 45 mol% to about 50 mol% of the resin, and base sulfo-aliphatic diols are selected in an amount of about 1 mol% to about 10 mol% of the resin.

[0050] Examples of organic diacids or diesters selected for the preparation of crystalline polyester resins include: oxalic acid, succinic acid, glutaric acid, adipic acid, octanoic acid, azelaic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, naphthalene-2,7-dicarboxylic acid, cyclohexanedicarboxylic acid, malonic acid and succinic acid, their diesters or anhydrides; and basic sulfonated organic diacids, such as the sodium, lithium or potassium salts of: dimethyl-5-sulfoisophthalic acid, dialkyl-5-sulfoisophthalic acid-4... - Sulfono-1,8-naphthalenedicarboxylic anhydride, 4-sulfonophthalic acid, dimethyl-4-sulfonophthalic acid, dialkyl-4-sulfonophthalic acid, 4-sulfophenyl-3,5-dimethyl esterbenzene, 6-sulfono-2-naphthyl-3,5-dimethyl esterbenzene, sulfonoterephthalic acid, dimethylsulfonoterephthalic acid, 5-sulfonoisophthalic acid, dialkylsulfonoterephthalic acid, sulfono-p-hydroxybenzoic acid, N,N-di(2-hydroxyethyl)-2-aminoethane sulfonate, or mixtures thereof. The organic diacid is selected in an amount of, for example, about 40 mol% to about 50 mol% of the resin, and the amount of the basic sulfoaliphatic diacid may be selected in an amount of about 1 mol% to about 10 mol% of the resin.

[0051] Suitable crystalline polyester resins include those disclosed in U.S. Patent No. 7,329,476 and U.S. Patent Application Publications Nos. 2006 / 0216626, 2008 / 0107990, 2008 / 0236446, and 2009 / 0047593, each of which is incorporated herein by reference in its entirety. In embodiments, a suitable crystalline resin may comprise a resin consisting of a mixture of ethylene glycol or nonanediol and dodecanoic acid and fumaric acid comonomers, having the following formula (II):

[0052]

[0053] Where b is approximately 5 to approximately 2000, and d is approximately 5 to approximately 2000.

[0054] If a semi-crystalline polyester resin is used herein, the semi-crystalline resin may include poly(3-methyl-1-butene), poly(hexamethylene carbonate), poly(ethylene-p-carboxyphenoxy-butyrate), poly(ethylene-vinyl acetate), poly(docosahexadecyl acrylate), poly(dodecyl acrylate), poly(octadecyl acrylate), poly(octadecyl methacrylate), poly(docosahexadecyl polyethoxyethyl methacrylate), poly(ethylidene adipate), poly(decamethylene adipate), poly(decamethylene azelate), poly(hexamethylene oxalate), poly(decamethylene oxalate), poly(ethylene oxide), poly(propylene oxide), poly(butane oxide), poly(decamethylene oxide), poly(decamethylene sulfide), poly(decamethylene disulfide), poly(... Ethylene sebacate, poly(decamethylene sebacate), poly(ethylene octanoate), poly(decamethylene succinate), poly(eicosemethylene malonate), poly(ethylene-p-carboxyphenoxyundecanoate), poly(ethylene dithiophthalate), poly(ethylene glycol methyl terephthalate), poly(ethylene-p-carboxyphenoxyvalerate), poly(hexamethylene-4,4-oxydibenzoate), poly(10-hydroxydecanoic acid), poly(isophthalaldehyde), poly(octadecylmethylene dodecanoate), poly(dimethylsiloxane), poly(dipropylsiloxane), poly(tetramethylene phthalate), poly(tetramethylene trithiocarboxylate), poly(trimethylene dodecanoate), poly(m-xylene), poly(p-xylylmethylformamide), and combinations thereof.

[0055] The amount of crystalline polyester resin in the toner particles of this disclosure, whether in the core, in the shell or both, may be in the following amounts: from 1% to 15% by weight of the toner particles (i.e., toner particles excluding external additives and water), from about 5% to about 10% by weight in the embodiments, and from about 6% to about 8% by weight in the embodiments.

[0056] In embodiments, the toner of this disclosure may further comprise at least one high molecular weight branched or crosslinked amorphous polyester resin. In embodiments, the high molecular weight resin may comprise, for example, branched amorphous resin or amorphous polyester, crosslinked amorphous resin or amorphous polyester, or mixtures thereof, or a non-crosslinked amorphous polyester resin that has already been crosslinked. According to this disclosure, about 1% to about 100% by weight of the high molecular weight amorphous polyester resin may be branched or crosslinked; in embodiments, about 2% to about 50% by weight of the higher molecular weight amorphous polyester resin may be branched or crosslinked.

[0057] As used herein, high molecular weight amorphous polyester resins may have a number average molecular weight (Mn) of, for example, about 1,000 to about 10,000, in embodiments about 2,000 to about 9,000, in embodiments about 3,000 to about 8,000, and in embodiments about 6,000 to about 7,000, as measured by gel permeation chromatography (GPC). When measured by GPC using polystyrene standards, the resin has a weight average molecular weight (Mw) greater than 55,000, for example, about 55,000 to about 150,000, in embodiments about 60,000 to about 100,000, in embodiments about 63,000 to about 94,000, and in embodiments about 68,000 to about 85,000. As measured by GPC relative to a standard polystyrene reference resin, the polydispersity index (PD) is greater than about 4, such as, for example, greater than about 4, from about 4 to about 20 in embodiments, from about 5 to about 10 in embodiments, and from about 6 to about 8 in embodiments. The PD index is the ratio of weight-average molecular weight (Mw) to number-average molecular weight (Mn). Low molecular weight amorphous polyester resins may have acid values ​​of from about 8 mg KOH / g to about 20 mg KOH / g, from about 9 mg KOH / g to about 16 mg KOH / g in embodiments, and from about 11 mg KOH / g to about 15 mg KOH / g in embodiments. High molecular weight amorphous polyester resins available from various sources may have various melting points, for example, from about 30°C to about 140°C, from about 75°C to about 130°C in embodiments, from about 100°C to about 125°C in embodiments, and from about 115°C to about 121°C in embodiments.

[0058] As determined by differential scanning calorimetry (DSC), high molecular weight amorphous resins available from various sources may have various initial glass transition temperatures (Tg), for example, from about 40°C to about 80°C, from about 50°C to about 70°C in an embodiment, and from about 54°C to about 68°C in an embodiment. In an embodiment, linear and branched amorphous polyester resins may be saturated or unsaturated resins.

[0059] High molecular weight amorphous polyester resins can be prepared by branching or crosslinking linear polyester resins. Branching agents, such as trifunctional or polyfunctional monomers, can be used, which typically increase the molecular weight and polydispersity of the polyester. Suitable branching agents include glycerol, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, diglycerol, trimellitic acid, trimellitic anhydride, pyromellitic acid, pyromellitic anhydride, 1,2,4-cyclohexanetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, and combinations thereof. These branching agents can be used in effective amounts from about 0.1 mol% to about 20 mol% depending on the starting diacid or diester used to prepare the resin.

[0060] Compositions comprising modified polyester resins having polycarboxylic acids that can be used to form high molecular weight polyester resins include those disclosed in U.S. Patent No. 3,681,106, as well as branched or crosslinked polyesters derived from polyvalent acids or alcohols, such as those shown in U.S. Patent Nos. 4,863,825, 4,863,824, 4,845,006, 5,143,809, 5,057,596, 4,988,794, 4,981,939, 4,980,448, 4,933,252, 4,931,370, 4,917,983, and 4,973,539, the full disclosures of which are incorporated herein by reference.

[0061] In embodiments, the crosslinked polyester resin may be made of a linear amorphous polyester resin containing unsaturated sites capable of reacting under free radical conditions. Examples of such resins include those disclosed in U.S. Patent Nos. 5,227,460, 5,376,494, 5,480,756, 5,500,324, 5,601,960, 5,629,121, 5,650,484, 5,750,909, 6,326,119, 6,358,657, 6,359,105, and 6,593,053, the full disclosures of which are incorporated herein by reference. In an embodiment, a suitable unsaturated polyester matrix resin may be prepared from diacids and / or anhydrides (such as, for example, maleic anhydride, terephthalic acid, trimellitic acid, fumaric acid, etc., and combinations thereof) and diols (such as, for example, bisphenol A ethylene oxide adduct, bisphenol A propylene oxide adduct, etc., and combinations thereof). In an embodiment, a suitable polyester is poly(propoxylated bisphenol A cofumaric acid).

[0062] In embodiments, crosslinked branched polyesters can be used as high molecular weight amorphous polyester resins. Such polyester resins can be formed from at least two pregelation compositions comprising at least one polyol or ester thereof having two or more hydroxyl groups, at least one aliphatic or aromatic polyfunctional acid or ester thereof, or a mixture thereof having at least three functional groups; and optionally at least one long-chain aliphatic carboxylic acid or ester thereof, or an aromatic monocarboxylic acid or ester thereof, or a mixture thereof. The two components can be reacted substantially completely in separate reactors to produce a first composition comprising a pregel having carboxyl end groups in a first reactor, and a second composition comprising a pregel having hydroxyl end groups in a second reactor. The two compositions can then be mixed to form a crosslinked branched polyester high molecular weight resin. Examples of such polyesters and methods of synthesis include those disclosed in U.S. Patent No. 6,592,913, the disclosure of which is incorporated herein by reference in its entirety.

[0063] Suitable polyols may contain about 2 to about 100 carbon atoms and have at least two or more hydroxyl groups or esters thereof. Polyols may include glycerol, pentaerythritol, polyethylene glycol, polyglycerol, etc., or mixtures thereof. Polyols may include glycerol. Suitable glyceryl esters include glyceryl palmitate, glyceryl sebacate, glyceryl adipate, glyceryl triacetate, glyceryl tripropionate, etc. The polyol may be present in an amount of about 20% to about 30% by weight of the reaction mixture, and in embodiments about 22% to about 26% by weight of the reaction mixture.

[0064] Aliphatic polyfunctional acids having at least two functional groups may include saturated and unsaturated acids or esters thereof containing about 2 to about 100 carbon atoms, and in some embodiments about 4 to about 20 carbon atoms. Other aliphatic polyfunctional acids include malonic acid, succinic acid, tartaric acid, malic acid, citric acid, fumaric acid, glutaric acid, adipic acid, pimelic acid, sebacic acid, octanoic acid, azelaic acid, sebacic acid, etc., or mixtures thereof. Other aliphatic polyfunctional acids that may be used include dicarboxylic acids containing a C3 to C6 cyclic structure and its positional isomers, and include cyclohexanedicarboxylic acid, cyclobutanedicarboxylic acid, or cyclopropanedicarboxylic acid.

[0065] Aromatic polyfunctional acids having at least two functional groups that can be used include terephthalic acid, isophthalic acid, trimellitic acid, pyromellitic acid, and naphthalene 1,4-dicarboxylic acid, naphthalene 2,3-dicarboxylic acid, and naphthalene 2,6-dicarboxylic acid.

[0066] The aliphatic or aromatic polyfunctional acid may be present in an amount of about 40% to about 65% by weight of the reaction mixture, or in an embodiment, about 44% to about 60% by weight of the reaction mixture.

[0067] Long-chain aliphatic carboxylic acids or aromatic monocarboxylic acids may include those containing about 12 to about 26 carbon atoms, in embodiments about 14 to about 18 carbon atoms, or esters thereof. Long-chain aliphatic carboxylic acids may be saturated or unsaturated. Suitable saturated long-chain aliphatic carboxylic acids may include lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, ceric acid, etc., or combinations thereof. Suitable unsaturated long-chain aliphatic carboxylic acids may include dodecenoic acid, palmitoleic acid, oleic acid, linoleic acid, linolenic acid, erucic acid, etc., or combinations thereof. Aromatic monocarboxylic acids may include benzoic acid, naphthoic acid, and substituted naphthoic acids. Suitable substituted naphthoic acids may include naphthoic acids substituted with a straight-chain or branched alkyl group containing about 1 to about 6 carbon atoms, such as 1-methyl-2-naphthoic acid and / or 2-isopropyl-1-naphthoic acid. Long-chain aliphatic carboxylic acids or aromatic monocarboxylic acids may be present in an amount from about 0% by weight to about 70% by weight of the reaction mixture, in embodiments from about 15% by weight to about 30% by weight of the reaction mixture.

[0068] If desired, additional polyols, ionic substances, oligomers, or derivatives thereof may be used. These additional diols or polyols may be present in an amount from about 0% by weight to about 50% by weight of the reaction mixture. Additional polyols or their derivatives may include propylene glycol, 1,3-butanediol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexanediol, neopentyl glycol, triglycerides, trimethylolpropane, pentaerythritol, cellulose ethers, cellulose esters such as cellulose acetate, sucrose isobutyrate acetate, etc.

[0069] In the embodiments, the cross-linked branched polyesters used for high molecular weight amorphous polyester resins may include those obtained by the reaction of dimethyl terephthalate, 1,3-butanediol, 1,2-propanediol and pentaerythritol.

[0070] In embodiments, a high molecular weight resin, such as a branched polyester, may be present on the surface of the toner particles of this disclosure. The high molecular weight resin on the surface of the toner particles may also be particulate in nature, wherein the high molecular weight resin particles have a diameter of about 100 nanometers to about 300 nanometers, and in embodiments about 110 nanometers to about 150 nanometers.

[0071] Whether in any core, any shell, or both, the amount of high molecular weight amorphous polyester resin in the toner particles of this disclosure may be from about 25% to about 50% by weight of the toner, in embodiments from about 30% to about 45% by weight, and in other embodiments from about 40% to about 43% by weight of the toner (i.e., toner particles excluding external additives and water).

[0072] The ratio of crystalline resin to low molecular weight amorphous resin to high molecular weight amorphous polyester resin can be in the range of about 1:1:98 to about 98:1:1 to about 1:98:1, in the embodiment about 1:5:5 to about 1:9:9, in the embodiment about 1:6:6 to about 1:8:8.

[0073] The toners described herein (in embodiments, the toner cores described herein) may comprise one or a combination of styrene-acrylate copolymers. In embodiments, the resin is selected from the group consisting of styrene, acrylates, methacrylates, butadiene, isoprene, acrylic acid, methacrylic acid, acrylonitrile, and combinations thereof.

[0074] Exemplary polymers that can be used in toner resins include styrene acrylate, styrene butadiene, styrene methacrylate, and more specifically, poly(styrene-alkyl acrylate), poly(styrene-1,3-diene), poly(styrene-alkyl methacrylate), poly(styrene-alkyl acrylate-acrylic acid), poly(styrene-1,3-diene-acrylic acid), poly(styrene-alkyl methacrylate-acrylic acid), poly(alkyl methacrylate-alkyl acrylate), poly(alkyl methacrylate-aryl acrylate), poly(aryl methacrylate-alkyl acrylate), poly(methacrylate-alkyl acrylate), poly(methyl ... Alkyl acrylate-acrylic acid), poly(styrene-alkyl acrylate-acrylonitrile-acrylic acid), poly(styrene-1,3-diene-acrylonitrile-acrylic acid), poly(alkyl acrylate-acrylonitrile-acrylic acid), poly(styrene-butadiene), poly(methyl methacrylate-butadiene), poly(ethyl methacrylate-butadiene), poly(propyl methacrylate-butadiene), poly(butyl methacrylate-butadiene), poly(methyl acrylate-butadiene), poly(ethyl acrylate-butadiene), poly(propyl acrylate-butadiene), poly(butyl acrylate-butadiene), poly(styrene-butadiene), poly(styrene-butadiene) Poly(methyl methacrylate-isoprene), poly(methyl methacrylate-isoprene), poly(ethyl methacrylate-isoprene), poly(propyl methacrylate-isoprene), poly(butyl methacrylate-isoprene), poly(methyl methacrylate-isoprene), poly(ethyl methacrylate-isoprene), poly(propyl methacrylate-isoprene), poly(butyl methacrylate-isoprene), poly(styrene-propyl acrylate), poly(styrene-butyl acrylate), poly(styrene-butadiene-acrylic acid), poly(styrene-butadiene-methacrylic acid), poly(styrene-butadiene-propylene) Poly(styrene-butyl acrylate-acrylic acid), poly(styrene-butyl acrylate-acrylic acid), poly(styrene-butyl acrylate-methacrylic acid), poly(styrene-butyl acrylate-acrylonitrile), poly(styrene-butyl acrylate-acrylonitrile-acrylic acid), poly(styrene-butadiene), poly(styrene-isoprene), poly(styrene-butyl methacrylate), poly(styrene-butyl acrylate-acrylic acid), poly(styrene-butyl methacrylate-acrylic acid), poly(butyl methacrylate-butyl acrylate), poly(butyl methacrylate-acrylic acid), poly(acrylonitrile-butyl acrylate-acrylic acid), and combinations thereof. The polymer can be a block copolymer, a random copolymer, or an alternating copolymer.

[0075] In some embodiments, the resin is selected from the group consisting of: poly(styrene-butadiene), poly(methyl methacrylate-butadiene), poly(ethyl methacrylate-butadiene), poly(propyl methacrylate-butadiene), poly(butyl methacrylate-butadiene), poly(methyl methacrylate-butadiene), poly(ethyl methacrylate-butadiene), poly(propyl methacrylate-butadiene), poly(butyl methacrylate-butadiene), poly(styrene-isoprene), poly(methyl methacrylate-isoprene), poly(ethyl methacrylate-isoprene), poly(propyl methacrylate-isoprene), poly(butyl methacrylate-isoprene), poly(methyl methacrylate-isoprene). Isoprene), poly(ethyl acrylate-isoprene), poly(propyl acrylate-isoprene), poly(butyl acrylate-isoprene), poly(styrene-butyl acrylate), poly(styrene-butadiene), poly(styrene-isoprene), poly(styrene-butyl methacrylate), poly(styrene-butyl acrylate-acrylic acid), poly(styrene-butadiene-acrylic acid), poly(styrene-isoprene-acrylic acid), poly(styrene-butyl methacrylate-acrylic acid), poly(butyl methacrylate-butyl acrylate), poly(butyl methacrylate-acrylic acid), poly(styrene-butyl acrylate-acrylonitrile-acrylic acid), poly(acrylonitrile-butyl acrylate-acrylic acid), and combinations thereof.

[0076] In embodiments, resins, waxes, and other additives for forming the toner composition may be included, and it can be provided in the form of a dispersion including a surfactant. Furthermore, the toner particles can be formed by emulsion aggregation, wherein the resin and other components of the toner are placed in one or more surfactants to form an emulsion, causing the toner particles to aggregate and coalesce. The charge control agent of the present invention is deposited onto the surface of the toner during the wet portion of the method, and subsequently, optionally, the toner having the charge control agent thus treated is washed and dried and recovered. Therefore, in embodiments, the toner particles herein comprise emulsion-aggregated toner particles.

[0077] One, two, or more surfactants may be used. The surfactant may be selected from ionic and nonionic surfactants. The term "ionic surfactant" encompasses both anionic and cationic surfactants. In embodiments, a surfactant may be used such that it is present in amounts of about 0.01% by weight to about 5% by weight of the toner composition, for example, about 0.75% by weight to about 4% by weight of the toner composition, or in embodiments, about 1% by weight to about 3% by weight of the toner composition.

[0078] Examples of nonionic surfactants include polyvinyl alcohol, polyacrylic acid, cellulose methyl ether, methylcellulose, ethylcellulose, propylcellulose, hydroxyethylcellulose, carboxymethylcellulose, polyoxyethylene hexadecyl ether, polyoxyethylene lauryl ether, polyoxyethylene octyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene oil-based ether, polyoxyethylene dehydrated sorbitol monolaurate, polyoxyethylene stearyl ether, polyoxyethylene nonylphenyl ether, and dialkylphenoxy poly(vinyloxy)ethanol. CA-210, CA-520 CA-720 CO-890, CO-720 CO-290, CA-210 890 and 897 was purchased from Rhone-Poulenc Inc. An example of a suitable nonionic surfactant is [product name missing] purchased from Rhone-Poulenc Inc. 897, which is primarily composed of alkylphenol ethoxylates. Other examples of suitable nonionic surfactants include block copolymers of polyethylene oxide and polypropylene oxide, including those commercially available as SYNPERONIC PE / F, in the embodiments SYNPERONIC PE / F 108.

[0079] Available anionic surfactants include sulfates and sulfonates, sodium dodecyl sulfate (SDS), sodium dodecylbenzenesulfonate, sodium dodecylnaphthalene sulfate, dialkylbenzene alkyl sulfates and sulfonates (such as rosin acid, available from Aldrich), and... The brand's anionic surfactant. An example of a suitable anionic surfactant is that purchased from Daiichi Kogyo Seiyaku co. Ltd. R, RK and SC or TAYCA POWERBN2060, purchased from Tayca Corporation (Japan), is primarily composed of branched sodium dodecylbenzene sulfonate. In the embodiments, other suitable anionic surfactants include DOWFAX. TM 2A1, an alkyl diphenyl ether disulfonate available from The Dow Chemical Company. Combinations of these surfactants may be used. Combinations of these surfactants with any of the aforementioned anionic surfactants may be used in the embodiments.

[0080] Examples of typically positively charged cationic surfactants include alkylbenzyl dimethyl ammonium chloride, dialkylbenzyl ammonium chloride, lauryl trimethyl ammonium chloride, alkylbenzyl methyl ammonium chloride, alkylbenzyl dimethyl ammonium bromide, benzalkonium chloride, hexadecylpyridinium bromide, C12, C15, C17 trimethyl ammonium bromide, halide salts of quaternized polyoxyethylalkylamines, dodecylbenzyl triethyl ammonium chloride, and mixtures thereof. Specific examples include those purchased from Alkaril Chemical Company. and Purchased from Kao Chemicals (Benzalkonium chloride), etc. An example of a suitable cationic surfactant is [product name missing] purchased from Kao Corp. B-50, which is primarily composed of benzyl dimethyl alkyl ammonium chloride. Mixtures of these and other surfactants can be used in the implementation scheme.

[0081] Latex particles produced as described above can be added to a colorant to produce a toner. In an embodiment, the colorant may be in a dispersion. The colorant dispersion may include, for example, submicron colorant particles having a volume average diameter of about 50 nanometers to about 500 nanometers, and in an embodiment, a volume average diameter of about 100 nanometers to about 400 nanometers. The colorant particles may be suspended in an aqueous phase containing anionic surfactants, nonionic surfactants, or combinations thereof. Suitable surfactants include any of the surfactants described above. In an embodiment, the surfactant may be ionic and may be present in the dispersion in amounts of about 0.1% by weight to about 25% by weight of the colorant, and in an embodiment, about 1% by weight to about 15% by weight of the colorant.

[0082] Colorants that can be used to form toners according to this disclosure include pigments, dyes, mixtures of pigments and dyes, mixtures of pigments, mixtures of dyes, etc. The colorant can be, for example, carbon black, cyan, yellow, magenta, red, orange, brown, green, blue, purple, or mixtures thereof.

[0083] In embodiments where the colorant is a pigment, the pigment may be, for example, carbon black, phthalocyanine, quinacridone, or RHODAMINE B. TM Colors include red, green, orange, brown, purple, yellow, and fluorescent colorants.

[0084] Exemplary colorants include carbon black, such as REGAL Magnetite; Mobay magnetite, including MO8029 TM M08060 TM Columbia magnetite; MAPICO BLACKSTM And surface-treated magnetite; Pfizer magnetite, including CB4799 TM CB5300 TM CB5600 TM MCX6369 TM Bayer magnetite, including Bayferrox 8600 TM 8610 TM Northern Pigments magnetite, including NP-604 TM NP-608 TM Magnox magnetite, including TMB-100 purchased from Paul Uhlichand Company, Inc. TM Or TMB-104 TM HELIOGEN BLUE L6900 TM D6840 TM D7080 TM D7020 TM PYLAM OIL BLUE TM PYLAM OIL YELLOW TM Pigment Blue 1 TM PIGMENT VIOLET 1 purchased from Dominion Color Corporation, Ltd., Toronto, Ontario TM PIGMENT RED 48 TM , LEMONCHROME YELLOW DCC 1026 TM EDTOLUIDINE RED TM and BON RED C TM Derived from Hoechst's Novaper Myellow FGL TM HOSTAPERM PINK E TM ; and CINQUASIA MAGENTA purchased from EIDuPont de Nemours and Company TM. Other colorants include 2,9-dimethyl-substituted quinacridones and anthraquinone dyes (identified in Color Index as CI 60710, CI Disperse Red 15), diazo dyes (identified in Color Index as CI26050, CI Solvent Red 19, tetra(octadecylsulfonylamino)phthalocyanine), X-ketophthalocyanine pigments (listed in Color Index as CI 74160, CI Pigment Blue), Anthrathrene Blue (identified in Color Index as CI 69810, Special Gray X-2137, Aniline Yellow 3,3-dichloroacetoacetanilide), monoazo pigments (identified in Color Index as CI 12700, CI Solvent Yellow 16), nitroaniline sulfonamides (identified in Color Index as Fulong Yellow SE / GLN, CI Disperse Yellow 33,2,5-dimethoxy-4-sulfonylaniline phenylazo-4'-chloro-2,5-dimethoxyacetoacetanilide, Yellow), and others. 180 and Permanent Yellow FGL). Organically soluble dyes of high purity that can be used for gamut purposes include Neopen Yellow 075, Neopen Yellow 159, Neopen Orange 252, Neopen Red 336, Neopen Red 335, Neopen Red 366, Neopen Blue 808, Neopen Black X53, and Neopen Black X55, wherein the dye is selected in various suitable amounts, for example, from about 0.5% by weight to about 20% by weight of the toner, or in the embodiments, from about 5% by weight to about 18% by weight of the toner.

[0085] In the implementation scheme, examples of colorants include Pigment Blue 15:3 with “Color Index Number” 74160, Magenta Pigment Red 81:3 with “Color Index Number” 45160:3, Yellow 17 with “Color Index Number” 21105, and known dyes such as food dyes, yellow dyes, blue dyes, green dyes, red dyes, magenta dyes, etc.

[0086] In other embodiments, magenta pigment, pigment red 122 (2,9-dimethylquinacridone), pigment red 185, pigment red 192, pigment red 202, pigment red 206, pigment red 235, pigment red 269, and combinations thereof can be used as colorants.

[0087] In some implementations, the colorant includes black pigment, cyan pigment, or a combination thereof.

[0088] The resulting latex (optionally in a dispersion) and colorant dispersion may be stirred and heated to about 35°C to about 70°C, in an embodiment about 40°C to about 65°C, thereby producing colorant aggregates with a volume average diameter of about 2 micrometers to about 10 micrometers, and in an embodiment about 5 micrometers to about 8 micrometers.

[0089] Optionally, the wax may also be combined with the resin to form toner particles. When included, the wax may be present, for example, in an amount of about 1% to about 25% by weight of the toner particles, or in an embodiment, about 5% to about 20% by weight of the toner particles.

[0090] Optional waxes include, for example, waxes with a weight-average molecular weight of about 500 to about 20,000, and in embodiments about 1,000 to about 10,000. Suitable waxes include, for example, polyolefin waxes such as polyethylene, polypropylene, and polybutene waxes, such as those commercially available from Allied Chemical and Petrolite Corporation, such as POLYWAX from Baker Petrolite. TM Polyethylene wax, wax emulsion purchased from Michaelman, Inc. and Daniels Products Company, and EPOLENE N-15 available commercially from Eastman Chemical Products, Inc. TM And the VISCOL 550-P purchased from Sanyo Kasei KK TM (Low weight average molecular weight polypropylene); plant-based waxes, such as carnauba wax, rice wax, candelilla wax, sumac wax, and jojoba oil; animal-based waxes, such as beeswax; mineral-based and petroleum-based waxes, such as montan wax, ceresin, pure ceresin, paraffin wax, microcrystalline wax, and Fischer-Tropsch wax; ester waxes obtained from higher fatty acids and higher alcohols, such as octadecyl stearate and docosyl docosate; ester waxes obtained from higher fatty acids and monovalent or polyvalent lower alcohols, such as butyl stearate, propyl oleate, glyceryl monostearate, glyceryl distearate, and pentaerythritol tetrabenzyl ester; ester waxes obtained from higher fatty acids and polyvalent alcohol polymers, such as diethylene glycol monostearate, dipropylene glycol distearate, diglyceryl distearate, and triglyceryl tetrastearate; sorbitol higher fatty acid ester waxes such as sorbitol monostearate, and cholesterol higher fatty acid ester waxes such as cholesterol stearate. Examples of functionalized waxes that can be used include, for example, amines; amides, such as AQUA SUPERSLIP 6550 purchased from Micro Powder Inc. TM SUPERSLIP 6530 TM Fluorinated waxes, such as POLYFLUO 190 purchased from MicroPowder Inc.TM POLYFLUO 200 TM POLYSILK 19 TM POLYSILK 14 TM Mixed fluorinated amide waxes, such as MICROSPERSION 19, also purchased from Micro Powder Inc. TM Imide, ester, quaternary ammonium, carboxylic acid, or acrylic polymer emulsions, such as JONCRYL 74 from SC Johnson Wax. TM 89 TM 130 TM 537 TM and 538 TM ; and chlorinated polypropylene and polyethylene purchased from Allied Chemical and Petrolite Corporation, as well as SC Johnson wax. Mixtures and combinations of the aforementioned waxes may also be used in the embodiments. The wax may be included as, for example, a fuser roller stripper.

[0091] In embodiments, the toner composition can be prepared by an emulsion aggregation method, such as a method comprising optionally aggregating a mixture of optional waxes and any other desired or required additives in a surfactant as described above, and an emulsion containing the aforementioned resin, and then aggregating the aggregate mixture. The mixture can be prepared by adding optional waxes or other materials to the emulsion, which may also optionally be present in the dispersion containing the surfactant. The emulsion may be a mixture of two or more emulsions containing the resin. The pH of the resulting mixture can be adjusted using an acid such as, for example, acetic acid, nitric acid, etc. In embodiments, the pH of the mixture can be adjusted to about 2 to about 4.5. Additionally, in embodiments, the mixture can be homogenized. If the mixture is homogenized, homogenization can be achieved by mixing at about 4,000 rpm to about 6,000 rpm. Homogenization can be achieved by any suitable apparatus, including, for example, an IKA ULTRA. T50 probe homogenizer.

[0092] After preparing the above mixture, an agglomerating agent can be added to the mixture. Any suitable agglomerating agent can be used to form the toner. Suitable agglomerating agents include, for example, aqueous solutions of divalent or polyvalent cationic materials. The agglomerating agent can be, for example, polyaluminum halides such as polyaluminum chloride (PAC) or corresponding bromides, fluorides, or iodides; polyaluminum silicates such as polyaluminum sulfosilicate (PASS); and water-soluble metal salts, including aluminum chloride, aluminum nitrite, aluminum sulfate, potassium aluminum sulfate, calcium acetate, calcium chloride, calcium nitrite, calcium oxalate, calcium sulfate, magnesium acetate, magnesium nitrate, magnesium sulfate, zinc acetate, zinc nitrate, zinc sulfate, zinc chloride, zinc bromide, magnesium bromide, copper chloride, copper sulfate, and combinations thereof. In an embodiment, the agglomerating agent can be added to the mixture at a temperature below the glass transition temperature (Tg) of the resin.

[0093] The agglomerating agent may be added to the mixture used to form the toner, for example, in an amount of about 0.1% to about 8% by weight of the resin in the mixture, in an embodiment about 0.2% to about 5% by weight, and in other embodiments about 0.5% to about 5% by weight. This provides a sufficient amount of reagent for agglomeration.

[0094] To control particle aggregation and agglomeration, in embodiments, an agglomerating agent may be quantitatively added to the mixture over time. For example, the agent may be quantitatively added to the mixture over a period of about 5 minutes to about 240 minutes, or in embodiments about 30 minutes to about 200 minutes. The addition of the agent may also be carried out while the mixture is kept under stirring conditions, which are about 50 rpm to about 1,000 rpm in embodiments, about 100 rpm to about 500 rpm in other embodiments, and at a temperature below the glass transition temperature of the resin as described above, which is about 30°C to about 90°C in embodiments, or about 35°C to about 70°C in other embodiments.

[0095] The particles can be aggregated until a predetermined desired particle size is achieved. The predetermined desired particle size refers to the expected particle size determined before formation, and the particle size is monitored during the growth process until that size is reached. Samples can be taken during growth, and the average particle size can be analyzed, for example, using a Coulter counter. Therefore, aggregated particles can be obtained by maintaining an elevated temperature or slowly raising the temperature to, for example, from about 40°C to about 100°C, and holding the mixture at that temperature for about 0.5 hours to about 6 hours, or in this embodiment, about 1 hour to about 5 hours, while maintaining stirring. Once the predetermined desired particle size is reached, the growth process is stopped. In this embodiment, the predetermined desired particle size is within the aforementioned toner particle size range.

[0096] The growth and shaping of particles after the addition of the agglomerating agent can be achieved under any suitable conditions. For example, growth and shaping can be carried out under conditions in which aggregation and coalescence occur separately. For the separate aggregation and coalescence stages, the aggregation process can be carried out under shear conditions at elevated temperatures, for example, from about 40°C to about 90°C, or from about 45°C to about 80°C in the embodiments, which may be lower than the glass transition temperature of the resin as described above.

[0097] In the implementation scheme, a shell may be applied to the aggregated particles after aggregation but before coalescence.

[0098] Resins that can be used to form the shell include, but are not limited to, the amorphous resins described above for the core. Such amorphous resins can be low molecular weight resins, high molecular weight resins, or combinations thereof. In embodiments, the amorphous resin that can be used to form the shell according to this disclosure may include an amorphous polyester of formula I above.

[0099] In some embodiments, the amorphous resin used to form the shell may be crosslinked. For example, crosslinking can be achieved by combining the amorphous resin with a crosslinking agent (sometimes referred to as an initiator in embodiments herein). Examples of suitable crosslinking agents include, but are not limited to, free radical initiators or thermal initiators, such as organic peroxides and azo compounds suitable for forming a gel in the core as described above. Examples of suitable organic peroxides include diacyl peroxides, such as, for example, decanoyl peroxide, lauroyl peroxide, and benzoyl peroxide; ketone peroxides, such as, for example, cyclohexanone peroxide and methyl ethyl ketone; alkyl peroxide esters, such as, for example, tert-butyl peroxyneodecanate, 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane, tert-pentyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peracetate, tert-pentyl peracetate, tert-butyl peroxybenzoate, tert-pentyl peroxybenzoate, oo-tert-butyl-o-isopropyl-peroxycarbonate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, oo-tert-butyl-o-(2-ethylhexyl)peroxycarbonate, and oo-tert-pentyl-o-(2-ethylhexyl)peroxycarbonate; and alkyl peroxides, such as, for example, dicumyl peroxide, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, oo-tert-butyl-o-(2-ethylhexyl)peroxycarbonate, oo-tert-pentyl-o-(2-ethylhexyl)peroxycarbonate; and alkyl peroxides, such as, for example, dicumyl peroxide, 2,5-dimethyl-2,5-dimethyl-2,5-di(benzoylperoxy)hexane, oo-tert-butyl-o-(2-ethylhexyl)peroxycarbonate, oo-tert-pentyl-o-(2-ethylhexyl)peroxycarbonate. -Dimethyl 2,5-di(tert-butylperoxy)hexane, tert-butylisopropylbenzene peroxide, α-α-bis(tert-butylperoxy)diisopropylbenzene, di-tert-butylperoxide and 2,5-dimethyl 2,5-di(tert-butylperoxy)hexyne-3; alkyl hydroperoxides, such as, for example, 2,5-dihydroperoxy2,5-dimethylhexane, cumene hydroperoxide, tert-butyl hydroperoxide and tert-pentyl hydroperoxide, and alkyl hydroperoxides Oxyketals, such as, for example, n-butyl 4,4-di(tert-butylperoxy)valerate, 1,1-di(tert-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-di(tert-butylperoxy)cyclohexane, 1,1-di(tert-pentylperoxy)cyclohexane, 2,2-di(tert-butylperoxy)butane, ethyl 3,3-di(tert-butylperoxy)butyrate and ethyl 3,3-di(tert-pentylperoxy)butyrate, and combinations thereof. Examples of suitable azo compounds include 2,2'-azobis(2,4-dimethylvaleronitrile), azobis-isobutyronitrile, 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(methylbutyronitrile), 1,1'-azobis(cyanocyclohexane), other similar known compounds, and combinations thereof.

[0100] The crosslinking agent and amorphous resin can be combined for a sufficient time and at a sufficient temperature to form a crosslinked polyester gel. In an embodiment, the crosslinking agent and amorphous resin can be heated to a temperature of about 25°C to about 99°C, or in an embodiment about 30°C to about 95°C, for a period of about 1 minute to about 10 hours, or in an embodiment about 5 minutes to about 5 hours, to form a crosslinked polyester resin or polyester gel suitable for use as a shell.

[0101] When used, the crosslinking agent may be present in an amount from about 0.001% by weight to about 5% by weight of the resin, or in the embodiments, from about 0.01% by weight to about 1% by weight of the resin. The amount of CCA may be reduced in the presence of a crosslinking agent or initiator.

[0102] A single polyester resin can be used as the shell, or as described above, in an embodiment, the first polyester resin can be combined with other resins to form the shell. Multiple resins can be used in any suitable amount. In an embodiment, the first amorphous polyester resin, such as a low molecular weight amorphous resin of Formula I above, can be present in an amount from about 20% by weight to about 100% by weight of the total shell resin, and in an embodiment, from about 30% by weight to about 90% by weight of the total shell resin. Therefore, in an embodiment, the second resin, and in an embodiment, the high molecular weight amorphous resin, can be present in the shell resin in an amount from about 0% by weight to about 80% by weight of the total shell resin, and in an embodiment, from about 10% by weight to about 70% by weight of the shell resin.

[0103] After agglomerating to the desired particle size and applying any optional shell, the particles can then be aggregated into the desired final shape. This agglomeration is achieved, for example, by heating the mixture to a temperature of about 45°C to about 100°C, or in an embodiment about 55°C to about 99°C (which may be at or above the glass transition temperature of the resin used to form the toner particles) and / or by reducing the stirring speed to, for example, about 100 rpm to about 400 rpm, or in an embodiment about 200 rpm to about 300 rpm. The shape factor or roundness of the fixing particles can be measured, for example, using a SYSMEX FPIA 3000 analyzer, until the desired shape is achieved.

[0104] The coalescence can be achieved in a timeframe of approximately 0.01 hours to approximately 9 hours, or approximately 0.1 hours to approximately 4 hours in the implementation scheme.

[0105] In an embodiment, after aggregation and / or coalescence, the pH of the mixture can then be lowered to about 3.5 to about 6, and in an embodiment to about 3.7 to about 5.5, using an acid, to further coalesce the toner aggregates. Suitable acids include, for example, nitric acid, sulfuric acid, hydrochloric acid, citric acid, and / or acetic acid. The amount of acid added can be from about 0.1% by weight to about 30% by weight of the mixture, and in an embodiment from about 1% by weight to about 20% by weight of the mixture.

[0106] The mixture can be cooled, washed, and dried. Cooling can be carried out at a temperature of about 20°C to about 40°C, or about 22°C to about 30°C in the embodiment, for a period of about 1 hour to about 8 hours, or about 1.5 hours to about 5 hours in the embodiment.

[0107] In one embodiment, the slurry can be passed through at least one heat exchanger to quench its temperature after coalescence. After coalescence, the mixture can be quenched to a temperature below the glass transition temperature of the resin, such as below about 40°C. Cooling can be rapid or slow, as needed. Suitable cooling methods may include introducing cold water into a jacket around at least one heat exchanger for quenching.

[0108] Subsequently, the toner slurry can be washed. Washing can be performed at a pH of about 7 to about 12, or in an embodiment at a pH of about 9 to about 11. Washing can be performed at a temperature of about 30°C to about 70°C, or in an embodiment at a temperature of about 40°C to about 67°C. Washing may include filtering and re-slurrying the filter cake containing the toner particles in deionized water. The filter cake may be washed once or multiple times with deionized water, or washed once with deionized water at a pH of about 4, wherein the pH of the slurry is adjusted with acid, and then optionally washed once or multiple times with deionized water.

[0109] Drying can be carried out at temperatures from about 35°C to about 75°C, and in the embodiments from about 45°C to about 60°C. Drying can continue until the moisture content of the particles is below the set target of about 1% by weight, and in the embodiments less than about 0.7% by weight.

[0110] The method described herein includes setting a charge control agent as described herein. In an embodiment, the emulsion agglomeration toner method of this invention includes: obtaining a latex of at least one resin; optionally, obtaining an aqueous dispersion of an optional colorant; optionally, obtaining an aqueous dispersion of an optional wax; forming a mixture of the latex of at least one resin, the aqueous dispersion of the optional colorant, and the aqueous dispersion of the optional wax; heating the mixture to a first temperature; maintaining the first temperature to form aggregated toner particles; adding a shell resin latex to form a shell on the aggregated particles; optionally, adding a solution of a chelating agent; stopping further aggregation and raising the temperature to a second temperature above the first temperature to cause the aggregated particles to agglomerate, thereby forming aggregated toner particles; cooling, optionally washing, and optionally drying to form emulsion agglomerated toner particles; introducing a charge control agent into the emulsion agglomerated toner particles to form a mixture containing the charge control agent. The emulsion aggregates toner particles; wherein the charge control agent comprises: at least one positively charged compound, wherein the at least one positively charged compound comprises a member selected from the group consisting of: amine compounds having at least 3 carbon atoms, ammonium compounds having at least 3 carbon atoms, phosphonium compounds having at least 3 carbon atoms, boronium compounds having at least 3 carbon atoms, and combinations thereof; at least one reactive anchoring compound, wherein the at least one reactive anchoring compound comprises a member selected from the group consisting of: amino, epoxy, carboxyl, hydroxyl, silanol, cyanide, and combinations thereof; and wherein the charge control agent optionally further comprises a negatively charged compound, wherein the negatively charged compound comprises a member selected from the group consisting of: aromatic carboxylic acids, silanols, phenols, pyranones, furans, and combinations thereof.

[0111] In an implementation scheme, the method further includes combining emulsion-aggregated toner particles with a toner carrier to form a color developer.

[0112] In embodiments, in addition to the internal charge control agents described herein, the toner particles herein may include optional additives as required or necessary. For example, the toner may include positive or negative charge control agents, for example, in an amount of about 0.1% to about 10% by weight of the toner, or in embodiments about 1% to about 3% by weight of the toner. Examples of suitable charge control agents include: quaternary ammonium compounds, including halogenated alkylpyridinium; hydrogen sulfates; alkylpyridinium compounds, including those disclosed in U.S. Patent No. 4,298,672, the disclosure of which is incorporated herein by reference in its entirety; organic sulfate and sulfonate compositions, including those disclosed in U.S. Patent No. 4,338,390, the disclosure of which is incorporated herein by reference in its entirety; hexadecylpyridinium tetrafluoroborate; distearate dimethylmethyl ammonium sulfate; aluminum salts, such as BONTRON E84. TM Or E88TM (Orient Chemical Industries, Ltd.); combinations thereof, etc. Such charge control agents can be applied simultaneously with the aforementioned shell resin or after the application of the shell resin.

[0113] It can also be blended after formation with external additive particles (including flow aids) of the toner particles, which may be present on the surface of the toner particles. Examples of these additives include metal oxides such as titanium oxide, silicon oxide, aluminum oxide, cerium oxide, tin oxide, and mixtures thereof; colloidal silica and amorphous silica, such as... Metal salts and metal salts of fatty acids (including zinc stearate and calcium stearate), or long-chain alcohols (such as UNILIN) TM 700), and mixtures thereof. In some embodiments, the toners described herein also contain cleaning additives selected from the group consisting of: stearates, cerium oxide, strontium titanate, and combinations thereof.

[0114] Each of these external additives may be present in amounts of about 0% to about 3% by weight of the toner, or in embodiments, about 0.25% to about 2.5% by weight of the toner, but the amount of the additive may be outside these ranges. In embodiments, the toner may include, for example, about 0% to about 3% by weight of titanium dioxide, about 0% to about 3% by weight of silica, and about 0% to about 3% by weight of zinc stearate.

[0115] In some implementations, the colorant does not contain (i.e., does not contain) TiO2 external additives.

[0116] In embodiments, the toners disclosed herein can be used as ultra-low melt (ULM) toners. In embodiments, dried toner particles with a core and / or shell, without external surface additives, may possess one or more of the following properties:

[0117] (1) The volume average diameter (also known as “volume average particle size”) is about 3 micrometers to about 25 micrometers (μm), about 4 μm to about 15 μm in some embodiments, and about 5 μm to about 12 μm in other embodiments.

[0118] (2) Number-average geometric particle size distribution (GSDn) and / or volume-average geometric particle size distribution (GSDv): In embodiments, the toner particles described in (1) above may have a narrow particle size distribution with a low numerical ratio of GSD of about 1.15 to about 1.38, or less than about 1.31 in other embodiments. The toner particles of this disclosure may also have a particle size such that the upper GSD by volume is in the range of about 1.20 to about 3.20, or in other embodiments, in the range of about 1.26 to about 3.11. The volume-average particle size D50V, GSDv, and GSDn may be measured by means of a measuring instrument such as a Beckman Coulter Multisizer 3 operated according to the manufacturer's instructions. Representative sampling may be performed as follows: a small amount of toner sample of about 1 gram may be obtained and filtered through a 25-micron sieve, then placed in an isotonic solution to obtain a concentration of about 10%, and then the sample is run in a Beckman Coulter Multisizer 3.

[0119] (3) The roundness is about 0.92 to about 0.99, and in other embodiments about 0.94 to about 0.975. The instrument used to measure particle roundness can be the FPIA-3000 manufactured by SYSMEX, following the manufacturer's instructions.

[0120] The properties of toner particles can be determined by any suitable technique and equipment, and are not limited to the instruments and techniques mentioned above.

[0121] The resulting toner particles can be formulated into a color developer composition. The toner particles can be mixed with carrier particles to achieve a two-component color developer composition. The toner concentration in the color developer can be from about 1% to about 25% by weight of the total color developer, and in the embodiments, from about 2% to about 15% by weight of the total color developer.

[0122] Examples of carrier particles that can be used to mix with toners include those particles capable of acquiring a charge of opposite polarity to that of the toner particles via triboelectricity. Exemplary examples of suitable carrier particles include particulate zirconium, particulate silicon, glass, steel, nickel, ferrite, ferroferrite, silicon dioxide, etc. Other carriers include those disclosed in U.S. Patent Nos. 3,847,604, 4,937,166, and 4,935,326.

[0123] The selected carrier particles can be used with or without a coating. In embodiments, the carrier particles may include a core having a coating, which may be formed from a mixture of polymers that are not in close proximity to each other in the triboelectric sequence. The coating may comprise a terpolymer of a fluoropolymer (such as polyvinylidene fluoride resin), styrene, methyl methacrylate and / or silanes (such as triethoxysilane), tetrafluoroethylene, other known coatings, etc. For example, polyvinylidene fluoride (e.g., under the trade name KYNAR 301F) may be used. TM The coating may be made of commercially available polyvinylidene fluoride (PVDF) and / or polymethyl methacrylate (PMMA) (e.g., having a weight-average molecular weight of about 300,000 to about 350,000, such as that commercially available from Soken). In embodiments, PVDF and PMMA may be mixed in a ratio of about 30% by weight to about 70% by weight to about 70% by weight to about 30% by weight, or in embodiments about 40% by weight to about 60% by weight to about 60% by weight to about 40% by weight. The coating may have a coating weight of, for example, about 0.1% by weight to about 5% by weight of the carrier, or in embodiments about 0.5% by weight to about 2% by weight of the carrier.

[0124] In the embodiments, PMMA may optionally be copolymerized with any desired comonomer, provided that the resulting copolymer maintains a suitable particle size. Suitable comonomers may include monoalkylamines or dialkylamines, such as dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, diisopropylaminoethyl methacrylate, or tert-butylaminoethyl methacrylate. The carrier particles may be prepared by mixing a carrier core with the polymer in an amount of about 0.05 wt% to about 10 wt%, or in the embodiments about 0.01 wt% to about 3 wt%, based on the weight of the coated carrier particles, until it adheres to the carrier core by mechanical impact and / or electrostatic attraction.

[0125] Various effective and suitable methods can be used to apply the polymer to the surface of the carrier core particles, such as cascade roller mixing, tumbling, grinding, shaking, electrostatic powder cloud spraying, fluidized bed, electrostatic disc processing, electrostatic curtain, and combinations thereof. The mixture of carrier core particles and polymer can then be heated to melt the polymer and fix it onto the carrier core particles. The coated carrier particles can then be cooled and sorted into the desired particle size.

[0126] In embodiments, a suitable carrier may include, for example, a steel core with a particle size of about 25 μm to about 100 μm, or in embodiments, about 50 μm to about 75 μm, coated with a conductive polymer mixture comprising, for example, methacrylate and carbon black, using the method described in U.S. Patent Nos. 5,236,629 and 5,330,874.

[0127] The carrier particles can be mixed with the toner particles in various suitable combinations. The concentration can be from about 1% to about 20% by weight of the toner composition. However, different percentages of toner and carrier can be used to obtain a colorimetric composition with the desired properties.

[0128] Toners can be used in electrostatic imaging or electrophotographic processes. In embodiments, any known type of image developing system can be used in the image developing apparatus, including, for example, magnetic brush development, skip-component development, hybrid scavengeless development (HSD), etc. These and similar developing systems are within the capabilities of those skilled in the art.

[0129] Imaging methods include, for example, preparing an image using an electrophotographic apparatus, which includes a charging component, an imaging component, a light guiding component, a developing component, a transfer component, and a fixing component. In embodiments, the developing component may include a color developer prepared by mixing a carrier with the toner composition described herein. The electrophotographic apparatus may include a high-speed printer, a black-and-white high-speed printer, a color printer, etc.

[0130] Once an image is formed with toner / developer using a suitable image development method such as any of the methods described above, the image can be transferred to an image receiving medium such as paper. In embodiments, the toner can be used to develop the image in an image developing apparatus using a fixing roller assembly. The fixing roller assembly is a contact fixing device within the capabilities of those skilled in the art, wherein heat and pressure from the roller can be used to fix the toner onto the image receiving medium. In embodiments, after or during melting onto the image receiving substrate, the fixing assembly can be heated to a temperature higher than the fixing temperature of the toner, for example, to about 70°C to about 160°C, in other embodiments about 80°C to about 150°C, and in still other embodiments about 90°C to about 140°C.

[0131] In embodiments where the toner resin is crosslinkable, this crosslinking can be achieved in any suitable manner. For example, the toner resin can be crosslinked during toner fixing to the substrate, wherein the toner resin is crosslinkable at the fixing temperature. Crosslinking can also be achieved by heating the fixed image to a temperature at which the toner resin will crosslink, for example, in a post-fixing operation. In embodiments, crosslinking can be performed at temperatures of about 160°C or lower, about 70°C to about 160°C in other embodiments, and about 80°C to about 140°C in still other embodiments.

[0132] Example

[0133] The following examples are provided to further define the various aspects of this disclosure. These examples are intended to be illustrative only and are not intended to limit the scope of this disclosure. Furthermore, unless otherwise specified, parts and percentages are by weight.

[0134] Polyester Particle Method. An aggregation / coalescing method is used to synthesize emulsion-aggregated toner particles. Core polyester latex, pigment, wax, nitric acid, and flocculant are homogenized and then aggregated in a reaction vessel at approximately 46°C under mixing. At a target particle size (D50v) of approximately 5.3 micrometers, a mixture of shell polyester latex and nitric acid is added, and the batch is held for a sufficient time to allow the latex to fully adhere to the existing toner aggregates. The pH is then increased to approximately 7.8 using sodium hydroxide and ethylenediaminetetraacetic acid (EDTA) to stop the aggregation reaction. The batch temperature is then raised to 85°C to aggregate the material into particles with a target sphericity of 0.972. Finally, the batch is passed through a heat exchanger to rapidly cool the toner particles to below 40°C. The resulting slurry is then washed and dried to produce stock toner masterbatches.

[0135] Table 1

[0136]

[0137]

[0138] A high MW (molecular weight) amorphous polyester was prepared in an emulsion from an amorphous polyester resin. The high MW amorphous polyester had an average molecular weight (Mw) greater than 70,000, an initial glass transition temperature (initial Tg) greater than 50°C, a particle size of about 70 nm, and a composition of bisphenol A terephthalate polyester resin with about 35% solids.

[0139] A low-MW amorphous polyester was prepared in an emulsion from an amorphous polyester resin. The low-MW amorphous polyester had a Mw of about 19,400, a Mn of about 5,000, an initial Tg of about 60°C, a particle size of about 170 nm to 230 nm, and a solids content of about 35%. The composition was a trimer-(propoxylated bisphenol A-terephthalate) trimer-(propoxylated bisphenol A-dodecenylsuccinate) trimer-(propoxylated bisphenol A fumarate).

[0140] Crystalline polyester is a crystalline polyester resin comprising a polyester prepared from dodecanoic acid and 1,9-nonanediol.

[0141] Carbon black is a non-oxidizing, low-structure furnace black pigment.

[0142] Cyan pigment is CI pigment blue 15:3.

[0143] Fischer-Tropsch wax is a distilled synthetic polymethylene wax with a melting point of about 92°C.

[0144] EDTA is ethylenediaminetetraacetic acid.

[0145] The parent particle formation process in all embodiments was as described above. All embodiments were prepared using the Fuji-mill mixing process and charge mapping analysis process described herein. The following embodiments use the same process, but differ in the type / amount of acid ligands and metal ion donors.

[0146] Toner preparation and mixing. All toner samples were mixed for 9 minutes at 9600 rpm with 70 to 75 grams of black particles and an additive packet containing fumed SiO2, colloidal SiO2, strontium titanate, cerium dioxide, and a wax for lubricating the photoresist using a 750 ml benchtop mixer (FujiMill). The mixer was run for 3 minutes, then turned off for 3 minutes (3 times) to prevent the mixing container from overheating and producing coarse particles.

[0147] Example 1

[0148] The source of the masterbatch in Example 1 was the aforementioned reserve polyester particles, which were retained after wet sieving and before filtrate removal and washing. Aliquots of a slurry containing approximately 13% solids (such that the slurry contains 5.0 kg of toner, on a dry weight basis) were placed in a mixing tank. A mixture of 5.0 g of 20% aminopropyl / methylsilsesquioxane and 30 g of deionized water was prepared to dilute the aminopropyl / methylsilsesquioxane to approximately 3% solution and added to the mixing tank via a peristaltic pump. The target addition time was 20 minutes. Next, the pH was adjusted from 8.3 to 4.5 by adding approximately 1,600 g of 0.3 M HNO3 solution. The batch was then stirred for 2 hours to uniformly coat the toner particles with aminopropyl / methylsilsesquioxane. The pH was then adjusted from approximately 5.1 to 7.8 by adding 1 N NaOH solution. Finally, the resulting slurry was washed and dried to produce dried, treated toner masterbatch. The treated particles, i.e., CCA-incorporated particles, were mixed using Fuji-Mill in the manner described above. The peak q / d values ​​of the A-region and J-region of the resulting toner were evaluated for mixing times of 5, 10, 15, and 30 seconds, and the results are provided in Tables 5 and 6.

[0149] Examples 2-4

[0150] Examples 2-4 were prepared in accordance with the method of Example 1, except that the amount of aminopropyl / methylsilsesquioxane was as shown in Table 2. The peak values ​​q / d in region A and region J of the resulting toners were evaluated for mixing times of 5, 10, 15, and 30 seconds, and the results are provided in Tables 5 and 6.

[0151] Comparative Example 5

[0152] Comparative Example 5 was prepared using the same masterbatch source as Examples 1-4, but without the application of aminopropyl / methylsilsesquioxane treatment. Aliquots of the slurry containing approximately 13% solids were aliquoted (so that the slurry contained 5.0 kg of toner, on a dry weight basis) and immediately washed and dried to produce dry toner masterbatch. The untreated particles were mixed using Fuji-Mill in the manner described above. The peak values ​​q / d in region A and region J of the resulting toner were evaluated for mixing times of 5, 10, 15, and 30 seconds, and the results are provided in Tables 5 and 6.

[0153] Table 2

[0154]

[0155]

[0156] Example 6

[0157] The source of the master particles in Example 6 was the aforementioned stock polyester particles after complete washing and drying. 80 g of the dried toner master particles were dispersed in a mixture of 360 g of deionized water and 20 g of ethanol. A mixture of 0.8 g of phenyltriethoxysilane and 5.0 g of ethanol was prepared and added dropwise to the dispersion while stirring for 2 hours. The resulting dispersion was then filtered, washed, and freeze-dried to produce dried, treated toner master particles. The treated particles were mixed using a Fuji-Mill mixer as described above. The peak values ​​q / d in region A and region J of the resulting toner were evaluated for mixing times of 5, 10, 15, and 30 seconds, and the results are provided in Tables 5 and 6.

[0158] Example 7

[0159] Example 7 was prepared in accordance with Example 6, except that the amount of phenyltriethoxysilane was as shown in Table 3. The peak values ​​q / d in region A and region J of the resulting toner were evaluated for mixing times of 5, 10, 15, and 30 seconds, and the results are provided in Tables 5 and 6.

[0160] Comparative Example 8

[0161] Comparative Example 8 was prepared using the same parent particle source as in Examples 6-7; however, no phenyltriethoxysilane treatment was applied. The untreated particles were mixed using Fuji-Mill in the manner described above. The peak values ​​q / d in region A and region J of the resulting toner were evaluated for mixing times of 5, 10, 15, and 30 seconds, and the results are provided in Tables 5 and 6.

[0162] Table 3

[0163] 6 1 7 2 Comparative Example 8 0

[0164] Example 9

[0165] The source of the master particles in Example 9 was the aforementioned reserve polyester particles, which were retained after wet sieving and before filtrate removal and washing. Aliquots of the slurry with approximately 13% solids (such that the slurry contains 5.0 kg of toner, on a dry weight basis) were placed in a mixing tank. A mixture of 15.0 g of 20% aminopropyl / methylsilsesquioxane and 85 g of deionized water was prepared to dilute the aminopropyl / methylsilsesquioxane to approximately 3% solution and added to the mixing tank via a peristaltic pump. The target addition time was 20 minutes. The pH was then adjusted from 8.3 to 4.5 by adding approximately 1,600 g of 0.3 M HNO3 solution. The batch was then stirred for 2 hours to uniformly coat the toner particles with the aminopropyl / methylsilsesquioxane. A mixture of 10.0 g of phenyltriethoxysilane and 190 g of ethanol was then prepared to dilute the phenyltriethoxysilane to a 5% solution and added to the dispersion via a peristaltic pump. The target addition time was 20 minutes. The batch was then stirred for another 2 hours. The pH was then adjusted from approximately 5.3 to 7.8 by adding 1N NaOH solution. Finally, the resulting slurry was washed and dried to produce dried, treated toner masterbatch particles. The treated particles were mixed using Fuji-Mill as described above. The peak values ​​q / d for region A and region J of the resulting toner were evaluated for mixing times of 5, 10, 15, and 30 seconds, and the results are provided in Tables 5 and 6.

[0166] Examples 10-13

[0167] Examples 10-13 were prepared in accordance with the method of Example 9, except that the amounts of aminopropyl / methylsilsesquioxane and phenyltriethoxysilane were as shown in Table 4. The A-region peak q / d and J-region peak q / d of the resulting toners were evaluated for mixing times of 5 seconds, 10 seconds, 15 seconds, and 30 seconds, and the results are provided in Tables 5 and 6.

[0168] Comparative Example 14

[0169] Comparative Example 14 was prepared using the same parent particle source as in Examples 9-13; however, no treatment with aminopropyl / methylsilsesquioxane or phenyltriethoxysilane was applied. The untreated particles were mixed using Fuji-Mill in the manner described above. The peak values ​​q / d in region A and region J of the resulting toner were evaluated for mixing times of 5, 10, 15, and 30 seconds, and the results are provided in Tables 5 and 6.

[0170] Table 4

[0171]

[0172] Evaluation Results. Each embodiment submitted a mixed charge distribution using a ferrite carrier at a concentration of 5% toner. In this process, a sample developer was prepared using a toner concentration of 5 parts per hundred parts (pph), where each 100 parts developer comprised 5 parts toner. After acclimatization at 80℉ and 80% relative humidity (RH) and 70℉ and 10% relative humidity, the samples were mixed using a Turbula mixer at 96 rpm for 10 minutes. Friction was measured using a Barbetta box, and charge spectrum (CSG) smears were taken at these 10-minute marks. 2.5 pph of fresh toner sample was added to the same developer (total TC = 7.5 pph), and mixed for 5, 10, 15, and 30 seconds using the same mixing settings. At each mixing time, CSG smears were taken to understand the mixing performance at each of the four mixing times. Each CSG smear was then converted into a graph plotting particle counts against q / d (charge / diameter, in fc / µm). The metrics in Tables 5 and 6 were calculated based on this data to provide a measure of the mixing rate of the colorimetric agent.

[0173] As shown in Tables 5 and 6, peak width is defined as the difference between the 98th and 2nd percentiles of the CSG, excluding tails and outliers. Low charge % is defined as a percentage of the CSG greater than -0.10 fc / µm and represents toner particles expected to be difficult to develop properly. Peak q / d is the local maximum value of the CSG, excluding those maximum values ​​appearing at the tail. This metric describes the magnitude of the triboelectric charge of the toner. Peak A / J is the ratio of peak q / d in region A to peak q / d in region J and represents the toner's ability to charge consistently under various environmental conditions.

[0174] The desired effect is a reduction of 5 seconds of peak width, an increase in the A / J ratio toward 1, and a minimization of the low charge percentage.

[0175] Data from Examples 1-4 show that the J-region charge -q / d (Table 5) decreases significantly with increasing amounts of aminopropyl / methylsilsesquioxane. Therefore, the A / J ratio is improved compared to the untreated Comparative Example 5, indicating consistent electrostatic copying performance under various environmental conditions. The A / J ratio of Example 3 is close to 1.0, which is ideal. Even at the lowest amounts of aminopropyl / methylsilsesquioxane (i.e., Example 1), this treatment shows a certain ability to reduce the peak width in the A-region (Table 6). In most cases, the low charge % increases, which is generally associated with charge reduction. This may hinder electrostatic copying performance in some cases.

[0176] Data from Examples 6 and 7 indicate that treatment with phenyltriethoxysilane has the potential to increase the charge in the A region and improve the A / J ratio compared to Comparative Example 8. This effect is most pronounced in Example 7, which contains the highest amount of phenyltriethoxysilane. Overall, except for Example 7, the charge distributions are similar in shape, although Example 7 contains a group of error-signed charges separated from the main distribution.

[0177] Data from Examples 9 through 13 detail the effects of the combined treatments of aminopropyl / methylsilsesquioxane and phenyltriethoxysilane. The A / J charge ratio was significantly improved compared to the untreated Comparative Example 14, with Example 9 showing particularly good results. Despite an overall decrease in charge, the combined treatments maintained strong performance even at low charge percentages. This was due to the narrow peak distribution, with the greatest improvement observed in the J region of Examples 9-12. In summary, the combined treatments enabled a good balance of performance across the various metrics considered. The combination of these treatments also enabled a significant improvement in performance compared to each treatment individually.

[0178] Table 5

[0179]

[0180] Table 6

[0181]

[0182]

[0183] It should be understood that various or alternatives of the features and functions disclosed above and other features and functions can be expected to be combined into many other different systems or applications. It should also be understood that those skilled in the art can subsequently make various substitutions, modifications, variations, or improvements that are not currently foreseen or anticipated, and these are also intended to be covered by the appended claims. Unless specifically stated in the claims, the steps or components of the claims should not imply or be introduced from the specification or any other claims into any particular order, quantity, position, size, shape, angle, color, or material.

Claims

1. An emulsion aggregation toner, said emulsion aggregation toner comprising: Toner particles, said toner particles comprising at least one resin; optional colorant; optional wax; and A reactive charge control agent, wherein the reactive charge control agent is disposed on the surface of the toner particles; The reactive charge control agent comprises: at least one positively charged compound, wherein the at least one positively charged compound comprises a member selected from the group consisting of: amine compounds having at least 3 carbon atoms, ammonium compounds having at least 3 carbon atoms, phosphonium compounds having at least 3 carbon atoms, boronium compounds having at least 3 carbon atoms, and combinations thereof; at least one reactive anchoring compound, wherein the at least one reactive anchoring compound comprises a member selected from the group consisting of: amino, epoxy, carboxyl, hydroxyl, silanol, cyanide, acid anhydride, aldehyde, ketone, vinyl, and combinations thereof; and wherein the reactive charge control agent optionally further comprises a negatively charged compound, wherein the negatively charged compound comprises a member selected from the group consisting of: aromatic carboxylic acids, silanols, phenol, pyranones, furanones, and combinations thereof; The reactive charge control agent comprises members of the group consisting of phenylsilanes, amino-sesquioxanes, and combinations thereof.

2. The emulsion aggregation toner according to claim 1, wherein the reactive charge control agent comprises aminopropyl-silsesquioxane.

3. The emulsion aggregation toner according to claim 1, wherein the reactive charge control agent comprises aminopropyl / methylsilsesquioxane.

4. The emulsion-aggregated toner according to claim 1, wherein the toner particles comprise a core-shell structure; and The reactive charge control agent is disposed on the surface of the toner particle shell.

5. The emulsion aggregation colorant according to claim 1, wherein the emulsion aggregation colorant does not contain TiO2.

6. A color developer, said color developer comprising: Emulsion aggregates toner particles and toner carriers; The emulsion aggregate toner particles comprise: at least one resin; optional colorant; optional wax; and a reactive charge control agent disposed on the surface of the emulsion aggregate toner particles; The reactive charge control agent comprises: at least one positively charged compound, wherein the at least one positively charged compound comprises a member selected from the group consisting of: amine compounds having at least 3 carbon atoms, ammonium compounds having at least 3 carbon atoms, phosphonium compounds having at least 3 carbon atoms, boronium compounds having at least 3 carbon atoms, and combinations thereof; at least one reactive anchoring compound, wherein the at least one reactive anchoring compound comprises a member selected from the group consisting of: amino, epoxy, carboxyl, hydroxyl, silanol, cyanide, acid anhydride, aldehyde, ketone, vinyl, and combinations thereof; and wherein the reactive charge control agent optionally further comprises a negatively charged compound, wherein the negatively charged compound comprises a member selected from the group consisting of: aromatic carboxylic acids, silanols, phenol, pyranones, furanones, and combinations thereof; The reactive charge control agent comprises members of the group consisting of phenylsilanes, amino-sesquioxanes, and combinations thereof.

7. The color developer according to claim 6, wherein the emulsion-aggregated colorant particles comprise a core-shell structure; and The reactive charge control agent is disposed on the surface of the emulsion aggregate toner particle shell.

8. The colorimetric agent according to claim 6, wherein the reactive charge control agent comprises aminopropyl-silsesquioxane.

9. The colorimetric agent according to claim 6, wherein the reactive charge control agent comprises aminopropyl / methylsilsesquioxane.

10. The color developer according to claim 6, wherein the emulsion aggregated colorant particles are free of TiO2.

11. An emulsion aggregation toner, said emulsion aggregation toner comprising: Toner particles, said toner particles comprising at least one resin; optional colorant; optional wax; and A reactive charge control agent, wherein the reactive charge control agent is disposed on the surface of the toner particles; The reactive charge control agent comprises members of the group consisting of phenylsilanes, amino-sesquioxanes, and combinations thereof.

12. The emulsion aggregation toner according to claim 11, wherein the reactive charge control agent comprises aminopropyl-silsesquioxane.

13. The emulsion aggregation toner of claim 11, wherein the reactive charge control agent comprises aminopropyl / methylsilsesquioxane.

14. A color developer, said color developer comprising: Emulsion aggregates toner particles and toner carriers; The emulsion aggregate toner particles comprise: at least one resin; optional colorant; optional wax; and a reactive charge control agent disposed on the surface of the emulsion aggregate toner particles; The reactive charge control agent comprises members of the group consisting of phenylsilanes, amino-sesquioxanes, and combinations thereof.

15. The colorimetric agent according to claim 14, wherein the reactive charge control agent comprises aminopropyl-silsesquioxane.

16. The colorimetric agent according to claim 14, wherein the reactive charge control agent comprises aminopropyl / methylsilsesquioxane.

17. A method for emulsion aggregation toner, the method comprising: To obtain a latex of at least one resin; To obtain an aqueous dispersion of the colorant; To obtain an aqueous dispersion of wax; A mixture of the latex containing at least one resin, the aqueous dispersion of the colorant, and the aqueous dispersion of the wax; The mixture is heated to a first temperature; Maintain the first temperature to form aggregated toner particles; Latex containing shell resin is added to form a shell on the aggregated toner particles; Optionally, a solution containing a chelating agent; Further aggregation is stopped and the temperature is raised to a second temperature above the first temperature to cause the aggregated toner particles to coalesce, thereby forming emulsion aggregated toner particles; Cooling, optionally washing, optionally drying, and recovering the emulsion aggregated toner particles; A reactive charge control agent is introduced into the emulsion aggregate toner particles to form emulsion aggregate toner particles containing the reactive charge control agent; The reactive charge control agent comprises: at least one positively charged compound, wherein the at least one positively charged compound comprises a member selected from the group consisting of: amine compounds having at least 3 carbon atoms, ammonium compounds having at least 3 carbon atoms, phosphonium compounds having at least 3 carbon atoms, boronium compounds having at least 3 carbon atoms, and combinations thereof; at least one reactive anchoring compound, wherein the at least one reactive anchoring compound comprises a member selected from the group consisting of: amino, epoxy, carboxyl, hydroxyl, silanol, cyanide, acid anhydride, aldehyde, ketone, vinyl, and combinations thereof; and wherein the reactive charge control agent optionally further comprises a negatively charged compound, wherein the negatively charged compound comprises a member selected from the group consisting of: aromatic carboxylic acids, silanols, phenol, pyranones, furanones, and combinations thereof. The reactive charge control agent comprises members of the group consisting of phenylsilanes, amino-sesquioxanes, and combinations thereof.

18. The emulsion aggregation toner method according to claim 17, further comprising: The emulsion aggregates toner particles and combines them with a toner carrier to form a color developer.

19. The emulsion aggregation toner method according to claim 17, wherein the reactive charge control agent comprises aminopropyl-silsesquioxane.

20. The emulsion aggregation toner method according to claim 17, wherein the reactive charge control agent comprises aminopropyl / methylsilsesquioxane.

21. The emulsion aggregation toner method according to claim 17, wherein the emulsion aggregation toner particles do not contain TiO2.

Citation Information

Patent Citations

  • Toner comprising charge control agent

    US12517445B2

  • Ultra low melt toners comprised of crystalline resins

    US20060216626A1

  • Toner compositions

    US20080107990A1

  • Toner processes

    US20080236446A1

  • Toner compositions and processes

    US20090047593A1